Government of Sierra Leone Education Data Hub: A User Research Report - Freiermuth, Sophie; Bedoui, Claire; Middleton, Emily; Taddese, Abeba (EdTech Hub, 2020)
Report on the Government of Sierra Leone Education Data Hub
Keywords: C:Sierra Leone; ES:Educational data; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

EdTech in Sierra Leone: A Rapid Scan - Mullan, Joel; Taddese, Abeba (EdTech Hub, 2020)
EdTech Hub country scans explore factors that enable and hinder the use of technology in education. This includes policies, government leadership, private sector partnerships, and digital infrastructure for education. The scans are intended to be comprehensive but are by no means exhaustive; nonetheless, we hope they will serve as a useful starting point for more in-depth discussions about opportunities and barriers in EdTech in specific countries and in this case, in Sierra Leone. This report is based primarily on desk research, with quality assurance provided by a country expert.
Keywords: C:Sierra Leone; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH

Sierra Leone : Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund. African Dept. (2019)
The Government of Sierra Leone’s new Medium-term National Development Plan (MTNDP) 2019–2023 has been founded on a strong political commitment to deliver devel-opment results that would improve the welfare of Sierra Leone’s citizens. The plan charts a clear path towards 2023 en route to the goal of achieving middle-income status by 2039 through inclusive growth that is sustainable and leaves no one behind. For the next five years, the Free Quality School Education Programme is the government’s flagship programme to provide a solid base to enhance human capital development and to facilitate the transformation of the economy.

Sierra Leone Multiple Indicator Cluster Survey 2017 - Statistics Sierra Leone (Statistics Sierra Leone, 2018)

The Sierra Leone Teachers Union: Labor in a Post-Conflict Society - Amman, John; O'Donnell, James (WorkingUSA, 2011)
The Sierra Leone Teachers Union (SLTU) has long played an important role in the country's education system and its labor movement. With more than 30,000 members, the SLTU is the largest and perhaps the most powerful union in Sierra Leone today. Nonetheless, the union struggles with challenges unheard of in developed countries. It represents teachers in an education system that was ravished by its eleven-year civil war (1991 to 2002). Not only are working conditions extremely difficult for teachers (classroom overcrowding, lack of educational materials, low pay, and often late pay), the union must negotiate union agreements with the Ministry of Education, which itself has no direct influence on the nation's coffers. Sierra Leone's Ministry of Finance and more importantly, the International Monetary Fund set policies that directly impact the quality of Sierra Leone's education system and its teachers.

Outputs Register: The Impact of GIS-Supported Teacher Allocation in Sierra Leone - Haßler, Björn; McBurnie, Chris; Beoku-Betts, Iman; Frazer, Madleen Madina (EdTech Hub, 2023)
EdTech Hub, Fab Inc, and the Education Workforce Initiative have produced the outputs listed in this document as part of the EdTech Hub-commissioned research project on ‘GIS-supported teacher allocation in Sierra Leone’. This research project began in January 2022. This document lists all outputs produced under this project. All outputs are available to the public via the EdTech Hub Evidence Library. An output of the EdTech Hub, https://edtechhub.org
Keywords: Author:OpenDevEd; HLR3; _C:Sierra Leone SLE; _r:AddedByZotZen

Factors Related to Teacher Absenteeism in Sierra Leone: Literature review - Vijil, Alejandra; McBurnie, Chris; Bellinger, Amy; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone (Hub-Led Research Programme 3). The education workforce is the most important school-level determinant of student learning. In Sierra Leone, the pupil-to-qualified-teacher ratio rises from 44:1 for schools in urban centres to 76:1 for schools in rural areas. Meanwhile, an average of a quarter of the workforce is absent from school on any given day. This informal literature review provides a summary of the most recent literature on teacher absenteeism, covering a wide range of low- and middle-income countries, including Sierra Leone, where the larger study is being undertaken. For the purposes of this review, we have focused on lessons learnt from sub-Saharan African studies that share similar education contexts and challenges as Sierra Leone. Based on the review, we hypothesise that distance from a teacher’s home to their school and their ability to choose which school they would like to work in impact teacher motivation, school attendance, and time on task. Efficient teacher allocation could improve each of these outcome estimates. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone : Poverty Reduction Strategy Paper-Progress Report (2005-2007) - International Monetary Fund (2008)
This report describes the progress made in implementing the Poverty Reduction Strategy Paper for Sierra Leone covering the period 2005–07. Efforts to reform the public sector were not successful. Management and Functional Reviews were conducted for several ministries, departments, and agencies but the recommendations were not implemented. A Senior Executive Service program was also developed but government and development partners could not agree on an implementation strategy and therefore the funds required for implementation were not provided.

Understanding Teacher School Choice Preferences: What Matters Most for Teacher Deployment in Sierra Leone? (EdTech Hub Preprint, 2023)
This exploratory mixed-methods study investigates the factors that shape where teachers want to work in Sierra Leone. We identify five dominant factors: monetary incentives, school conditions, opportunities for professional development and support, school location, and relationships with the school and the community. Importantly, these factors combine to push and pull teachers to different locations. Moreover, the factors interact with individual teacher characteristics such as gender, family status, and experience to influence school choice preferences. This set of factors — and their interaction with certain teacher characteristics — continues to shape preferences as teachers move up the career ladder. Keywords: Teacher deployment, teacher preferences, Sierra Leone, teacher supply, remote schools An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School-to-School Mobility Patterns and Retention Rates of Payroll Teachers in Sierra Leone - Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alisdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn (EdTech Hub, 2023)
This report is one of several on the research project on the Impact of GIS-Supported Teacher Allocation in Sierra Leone. Recent studies from this series have shown that being put on the government payroll can incentivise teachers to relocate to remote areas of the country. There is a concern, however, that being put on the payroll does not necessarily ensure the retention of teachers in these areas and that teachers will soon move to locations they consider more favourable. As there is no data on teacher mobility patterns and schools’ teacher retention rates, policies tend to be based on anecdotal evidence. This paper aims to fill this evidence gap by exploring teachers’ school-to-school mobility trends and retention rates using the Annual School Census (ASC) data from 2015 to 2021. Using data on teachers’ individual characteristics, as well as geospatial location data of each school, the paper explores whether mobility patterns vary by teachers’ gender or qualifications and whether the teaching workforce is urbanising. While studies have looked at teacher retention, this study is the first in a low-income country to use school census data to create a panel dataset to study teachers’ movements and school retention rates over time. Keywords: teacher mobility; teacher retention rates; mobility patterns; teacher deployment; Sierra Leone; education An output of the EdTech Hub https://edtechhub.org
Keywords: _r:AddedByZotZen

Teacher Deployment in Sierra Leone: Lessons learnt and going forward - Beoku-Betts, Iman (EdTech Hub, 2023)
This report provides an overview of the teacher deployment process in Sierra Leone prior to and including 2022. Through interviews with key stakeholders in the Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC), we look at lessons learnt from the deployment process and next steps for how teacher deployment can be implemented. Although there are a number of volunteer teachers in Sierra Leone, the TSC are aiming to increase the number of qualified teachers on the government payroll as well as retaining teachers in rural areas. It was noted that teachers from rural areas being put on the government payroll and deployed to rural schools are better placed to teach in rural schools than teachers moving from urban to rural areas. Hpwever, it is still challenging to find qualified teachers in these rural areas. The TSC want to look at how they can target teachers to take up rural positions, either through distance learning to gain the right qualifications or working with teacher training institutions (TTIs) to prioritise schools in rural areas for placement. Overall, the TSC want to use data as the basis for decision-making on deploying teachers equitably. Keywords Teacher deployment; teacher training; unqualified teachers; volunteer teachers; rural schools; data for decision-making An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

School Leaders’ Preferences on School Location in Sierra Leone: An individual and school-level study - Espinoza-Revollo, Patricia; Ramirez, Ana; Atherton, Paul; Mackintosh, Alasdair (EdTech Hub, 2022)
Attracting qualified teachers to remote areas is a challenge in Sierra Leone. The pupil-to-qualified-teacher ratio in rural areas is 76:1, rising to 83:1 for schools located more than 15 km away from urban centres — well above the national target of 40:1. As equitable teacher deployment is crucial to ensure high-quality education, the Teaching Service Commission (TSC) aims to increase the deployment of qualified teachers to the most remote areas of the country. This paper describes a quantitative survey of school leaders’ perceptions of what shapes school location preferences and what factors need to be in place (i.e., incentives) to address the imbalanced distribution of qualified teachers in the country. We used data from a text message survey sent to school leaders around the country. This paper accompanies a qualitative inquiry on the same topic: What Matters Most for Teacher Deployment? A case study on teacher school choice preferences in Sierra Leone. Together with the qualitative study, our findings aim to address a gap in empirical evidence on teacher school preferences in Sierra Leone and contribute to a growing literature on teachers’ preferences in low- and middle-income countries. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone Digital Learning Landscape Analysis: Developing the National Digital Learning Strategy - Waziri, Nafisa; Mufti, Abdal; Ramesh Vasudevan, Sharanya; Beoku-Betts, Iman; Oyedele, Oluwatomisin (EdTech Hub, 2025)
In 2024, the World Bank submitted a request to EdTech Hub's Helpdesk to support the Government of Sierra Leone in developing a National Digital Learning Strategy. The Hub initiated the process with the creation of this digital learning landscape analysis. The report identifies achievements and progress to date, as well as key challenges and priority areas going forward. It is based on primary and secondary data collection methods, including key informant interviews, focus group discussions, and a comprehensive desk review. Other relevant sources to gain insight into existing EdTech initiatives, interventions, and challenges within the country were also reviewed. Keywords: EdTech; National Digital Learning Strategy; landscape analysis; Ministry of Basic and Senior Secondary Education; Teaching Service Commission. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - Sierra Leone Education Innovation Challenge (2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More

Investigating the Activity Levels of School Quality Assurance Officers in Sierra Leone - Beoku-Betts, Iman; Leh Wi Lan (EdTech Hub, 2023)
Since the launch of the Free Quality School Education (FQSE) Programme in 2018, the Sierra Leone Ministry of Basic and Senior Secondary Education (MBSSE) has prioritised the use of data for decision-making across several education reform programmes. Part of this vision has been to build systems to measure school quality through School Quality Assurance Officers (SQAOs) using data collection and feedback. This system includes using tools for teacher management, lesson observations, school improvement, and attendance monitoring. This report presents findings from qualitative research conducted in three districts in Sierra Leone. The aim is to provide the MBSSE and other partners with insights to understand the variation in and what is needed to maximise SQAO activity levels, increase principal engagement with digital tools, and support and promote quality visits to schools. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone turns to technology and analytics to put quality back into education - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
Today, an estimated 2 million students return to school for the second year of the Free Quality School Education (FQSE) Program. The Government of Sierra Leone commits 21% of theRead More

‘Without Education You Can Never Become President’: Teenage Pregnancy and Pseudo-empowerment in Post-Ebola Sierra Leone - Menzel, Anne (Journal of Intervention and Statebuilding, 2019)
This article analyses the emergence of ‘teenage pregnancy’ as a new policy focus in post-Ebola Sierra Leone and explores how Sierra Leoneans interpret the problem of ‘teenage pregnancy’. I argue that the new policy focus is not indicative of changing or new problems. Rather, ‘teenage pregnancy’ has created opportunities for donors and the Government of Sierra Leone to continue cooperation in gender politics. At the same time, Sierra Leoneans are clearly concerned about ‘teenage pregnancy’, and many agree with sensitization campaigns that responsibilize young women and girls while downplaying structural factors that render them vulnerable to arrangements involving transactional sex.
Keywords: Sierra Leone; aid and development; gender politics; neoliberalism; sexual violence; teenage pregnancy

Does living in a community with more educated mothers enhance children's school attendance? Evidence from Sierra Leone - Kamanda, Mamusu; Madise, Nyovani; Schnepf, Sylke (International Journal of Educational Development, 2016)
In Sierra Leone girls are 23.4% less likely to attend secondary education than boys. This difference between sexes increases the gender gap in educational attainment since women's education is positively associated with children's educational wellbeing. This paper investigates the relationship between children's school attendance, their mothers’ level of education, as well as the overall level of women's education at the community level in Sierra Leone using multilevel statistical modelling techniques and the country's 2008 Demographic and Health Survey data. The findings suggest that, regardless of a child's own mother's education, an increase in the proportion of mothers with secondary or higher education in a community by 10% improves the probability of attending junior secondary school significantly by 8%; a 50% increase improves the likelihood of attending school by 45%. There was no significant relationship between the proportion of better educated mothers in a community and primary school attendance. However, relative to children whose mothers had no formal education, children whose mothers had attained primary, secondary or higher education were 7%, 14% and 22% more likely to attend primary school respectively. Future policies should seek to promote girls’ education at post-primary education and develop community based programmes to enable the diffusion and transmission of educational messages.
Keywords: Girls’ education; Mothers’ education; School attendance; Sierra Leone

EdTech Evidence From Covid-19 Response: A thematic review of primary research from Bangladesh, Ghana, Kenya, Pakistan and Sierra Leone - Nicolai, Susan; Jefferies, Kate; Stepanek Lockhart, Ashley (EdTech Hub, 2023)
To better understand the use of EdTech interventions as part of response to the Covid-19 pandemic, EdTech Hub commissioned ten small-scale research studies in five low- and middle-income countries: Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone. This paper includes insight into research methodologies across these studies, with particularly interesting findings on how EdTech effectiveness is being measured. A semi-structured thematic analysis further provides insights in relation to four main user groups of learners, girls, teachers, and parents and caregivers and points to a series of cross-cutting factors that are important for EdTech interventions in low-resource settings. An overarching takeaway centres on the fact that having technology in place is a small part of EdTech effectiveness, with wider teaching and learning ecosystems accompanying EdTech deserving more attention. Overall, the studies reveal a symbiotic relationship between people and technology, reinforcing that EdTech works best when users are involved across design, iteration, awareness building, and engagement. Keywords: EdTech, Covid-19, digital, education, learning, remote An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Sierra Leone series: Freetown Teachers College and its multimodal approach to teacher professional development - McBurnie, Chris; Moriba, Sambo; Brainard, Prince (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week two, we connected with Dr Samba Moriba and Prince Brainard from Freetown Teachers…
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodoETH; dode_eth-src-eth

Sierra Leone series: Plan International and the importance of community support for distance teacher professional development programmes - Saidu, Arthur; Casado, Eusebio Rincon; Shergill, Maggie; McBurnie, Chris (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.  In week four, we met with Arthur Saidu, Eusebio Rincon Casado and Maggie Shergill from…
Keywords: _DOILIVE; _EdTechHub_Output; ___working_potential_duplicate; _zenodoETH

Sierra Leone series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health. - Tahi (EdTech Hub, 2021)
Over the past few months, the EdTech Hub team has analysed and mapped the EdTech research landscape in Sierra Leone. In doing so, we have met a number of individuals and organisations that are exploring if and how technology can support the country’s education sector.   In week one, we connected with Abdulai Swaray and Bai Kamara from the Pikin-to-Pikin Movement.…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Sierra Leone Demographic and Health Survey 2008 - Statistics Sierra Leone (Ministry of Health and Sanitation, 2009)

Understanding Sierra Leonean and Liberian teachers’ views on discussing past wars in their classrooms - Shepler, Susan; Williams, James H. (Comparative Education, 2017)
Various curricular and textbook initiatives exist to aid in the national processes of coming to terms with past violence, often serving the political goals of the victors, sometimes supported by international transitional justice institutions. Sierra Leone and Liberia each experienced a devastating civil war during the 1990s and into the 2000s, and each is struggling to rebuild shattered education systems. In addition, each country has experienced a set of post-conflict transitional justice initiatives: Truth and Reconciliation Commissions in each, and a Special Court for Sierra Leone. Although their respective ministries of education have attempted to address peace education through UNICEF-sponsored curriculum revision processes, those efforts have not yet reached the majority of serving teachers, so a discussion of teachers’ actual practices is vital. This article uses interviews with teachers in rural and urban Sierra Leone and Liberia to discuss whether and how teachers talk about past war in their classrooms; whether they think it is important to discuss past conflicts, and if so, why; and what kind of curricular support would help them better teach about the wars. The article discusses how and why teachers embrace or subvert official efforts through their classroom practices, and compares the Sierra Leone and Liberia contexts and results. This research will help us to understand teachers’ own perspectives on addressing past conflict in their classrooms, and perhaps help policy-makers better implement their peace education initiatives.
Keywords: Education; Liberia; Sierra Leone; teachers; teaching about conflict; transitional justice

Sierra Leone: Price for 1GB mobile data 2023 - Galal, Saifaddin (Statista, 2024)
One gigabyte of mobile internet in Sierra Leone cost, on average, 0.67 U.S.

EdTech in Sierra Leone: Reimagining education for continuous learning and teaching - Sengeh, David Moinina (Global Partnership for Education, 2021)
Read how the government of Sierra Leone is using technology to address the profound ongoing teaching and learning crisis, and deliver inclusive, quality education.

Sierra Leone Multiple Indicator Cluster Survey 2017, survey findings report - Statistics Sierra Leone (Statistics Sierra Leone, 2017)

Sierra Leone: Historic bill to end child marriage passed - sustained efforts to raise community awareness must now follow - Amnesty International (Amnesty International, 2024)
Reacting to the signing into law of the Prohibition of Child Marriage Act 2024 on 2 July by President Julius Maada Bio, Samira Daoud, Amnesty International Regional Director for West and Central Africa, said: “We welcome this historic law banning child marriage in Sierra Leone. This legislation, in criminalizing marriage for anyone under the age […]

Teacher Retention and Mobility in Sierra Leone: What factors motivate teachers to stay at or leave schools? - Lurvink, Anne-Fleur; Mansaray, Kabiru; Kamara, Josephine; Khanu, Alimamy James; Cameron, Emma; Godwin, Katie; Haßler, Björn (EdTech Hub, 2023)
The current study is the third in a series of research studies, which aim to generate evidence that can support the MBSSE and TSC with their teacher allocation and deployment strategy. Our first study investigated teacher preferences for school choice and uncovered important considerations for teacher deployment. Following this, we investigated mobility patterns for teachers who are on the government payroll, and payroll teacher retention rates. The latter study helped us understand where teachers move to when they change schools, and also helped us identify areas with high (hot spots) and low retention rates (cold spots). The current study is explanatory in nature and aims to understand why teachers stay at or leave their schools. Keyword: teacher allocation; teacher retention; teacher mobility; Sierra Leone An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education service transformation in Sierra Leone: Where policy meets the people | Blog | Global Partnership for Education - Sengeh, David Moinina (2020)
As GPE prepares to launch a new five-year strategic plan responding to partner countries’ demands for transformative change, GPE Board Member and Minister of Basic and Senior Secondary Education David Moinina Sengeh shares learnings from his first year of office on what transforming education means to the people of Sierra Leone.

Sierra Leone Medium Term National Development Plan (Volume 1) - Ministry of Planning and Economic Development (Sierra Leone) (2019)

Sierra Leone designs online portal to take long wait out of teacher recruitment - Directorate of Science, Technology & Innovation (Sierra Leone) (2019)
A new teacher recruitment portal developed at the Directorate of Science, Technology, and Innovation (DSTI) will make it easier and faster for education administrators to hire teachers, and allocate teachersRead More

Leh Wi Lan: Improving The Quality Of Secondary Education In Sierra Leone - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)

Transforming education service delivery in Sierra Leone: from evidence to action - Sengeh, David Moinina; May-Wilson, Hannah (Global Partnership for Education, 2020)
Sierra Leone’s education system has been plagued by events that have challenged the effective delivery of high-quality education for every child for nearly three decades. But thanks to a program launched in 2018, the government is achieving greater access, quality, and equity for children by removing financial barriers to school enrollment and improving teaching and learning outcomes.

National Digital Learning Strategy for the Sierra Leone Ministry of Basic and Senior Secondary Education & Teaching Service Commission 2025–2030 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2025)
Sierra Leone launches first-ever National Digital Learning Strategy The Ministry of Basic and Senior Secondary Education (MBSSE) and the Teaching Service Commission (TSC) are pleased to announce the launch of Sierra Leone’s first-ever National Digital Learning Strategy (NDLS) — a groundbreaking framework aimed at leveraging educational technology to improve teaching and learning in Sierra Leone. Developed through a collaborative and consultative process with representatives from the MBSSE, TSC, Ministry of Tertiary and Higher Education (MTHE), Presidential Delivery Unit (PDU), and Ministry of Communications, Technology, and Innovation (MoCTI) and shaped by insights from students, teachers, district leaders and officials, the NDLS outlines key priorities related to addressing the digital divide in Sierra Leone; improving teachers’ digital capabilities; strengthening learners’ access to technology; improving access to localized content, and improving coordination mechanisms between all EdTech stakeholders. EdTech Hub is a proud partner of this work alongside the UK Foreign, Commonwealth and Development Office (FCDO), UNICEF, the World Bank, and other collaborators. This collaboration included technical guidance and support throughout the process. The NDLS represents a collective commitment to transforming education and building future-ready learners and educators.

Remote Supervision Options for School Quality Assurance Officers: Recommendations for a cost-effective and rapid develop-and-test process - Beoku-Betts, Iman; Ampofo, Rudolph; Haßler, Björn (EdTech Hub, 2024)
The Sierra Leone Secondary Education Improvement Programme II (SSEIP II) is a five-year programme funded by the UK Foreign, Commonwealth and Development Office (FCDO) to support the Ministry of Basic and Senior Secondary Education (MBSSE) to improve learning outcomes for students at secondary level and to increase the enrolment, retention and well-being of girls and children with disabilities in school. Part of the programme includes exploring the use of different digital tools for School Quality Assurance Officers (SQAOs), including tools for remote visits. In December 2022, the EdTech Hub collaborated with the Government of Sierra Leone and implementing partners of the Leh Wi Lan programme (continued under SSEIP II) to better understand what factors affect the variability in the activity levels of SQAOs and the level of engagement with digital tools by school principals. Based on the findings of this research, the SSEIP II project will look at supporting the MBSSE to formalise remote supervision options for the SQAOs, particularly for those with remote clusters. As part of this work, this report focuses on recommendations for how SQAOs can conduct remote school visits, particularly for schools in hard-to-reach areas.An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Worldreader | Sierra Leone - Worldreader (2020)
Worldreader brings digital reading to schools in Sierra Leone in partnership with the Klintworth Family Foundation.

Learning from Experience: A post-Covid-19 data architecture for a resilient education data ecosystem in Sierra Leone - Fab Inc. (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Sierra Leone 2015 population and housing census: Thematic report on poverty and durables - Statistics Sierra Leone (Statistics Sierra Leone, 2017)

Government–donor relations in Sierra Leone: Who is in the driving seat? - Harris, David; Conteh, Felix Marco (The Journal of Modern African Studies, 2020)
Since the cessation of conflict in 2002, Sierra Leone has experienced extraordinary levels of involvement from Western donors. Paradoxically, while relationships are often portrayed on the ground as strong with significant donor influence, our research shows considerable fluidity in individual and institutional relationships. The article disaggregates donor–government relations at various levels over a short but crucial period, 2010–16, asking in each case who occupies the driving seat. In so doing, the article interrogates the concept of ‘extraversion’, investigating to what extent government – and indeed donors – has space in which to manoeuvre and how and why government and donors act as they do in this space. The period 2010–16 is of particular interest due to extreme iron ore price volatility and the Ebola epidemic of 2014–15. The article adds much-needed critique and empirical evidence to the debate on donor influence and ‘extraversion’.

Sierra Leone invests $1.5 million to bring education innovation to schools for better learning outcomes - DSTI Media (Directorate of Science, Technology and Innovation, 2019)
A national education dashboard released last month by Sierra Leone’s agency for technology and innovation and the Ministry of Basic and Senior Secondary Education (MBSSE) showed that schools and studentsRead More

Redesigning an education project for child friendly radio: a multisectoral collaboration to promote children’s health, education, and human rights after a humanitarian crisis in Sierra Leone - Barnett, Sarah; van Dijk, Jetske; Swaray, Abdulai; Amara, Tamba; Young, Patricia (BMJ, 2018)
Sarah Barnett and colleagues describe how an educational project was rapidly adapted into a radio education programme after the 2014 Ebola epidemic in Sierra Leone

Sierra Leone’s Medium-Term National Development Plan 2019-2023: Education for Development. - Government of Sierra Leone (2019)

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.

How Do In-Service Communities of Practice Support Teacher Learning and What Role Can EdTech Play? - Adam, Taskeen; Friese, Laila; Plaut, Daniel (EdTech Hub, 2025)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at how in-service Communities of Practice (CoPs) support teacher learning and how EdTech can enhance this aspect of teacher professional development (TPD) in low- and middle-income countries. In-service CoPs have become an important component of TPD, creating spaces where teachers can share their knowledge and experiences, practice and reflect on pedagogical approaches, and support one another through classroom challenges. We focus on EdTech Hub’s work in design-based implementation research for TPD with particular reference to large-scale national TPD programmes in Tanzania, Malawi, and Sierra Leone. CoPs have been an essential part of these programmes. Cross-cutting insights and similarities identified across these programmes surface effective practices in designing and implementing CoPs, including the role of EdTech in enabling, supporting, or enhancing them. We present findings and recommendations that inform how various tech modalities used in CoPs have been instrumental in supporting TPD at the ‘teacher’, ‘school’, and ‘system’ levels. Lastly, we explore areas that require further research, namely, the need to measure the impact of CoPs, specifically regarding improved classroom instruction and learning outcomes. There is minimal information on the cost-effectiveness of CoPs and the use of technologies within them; this area merits further research. More testing could also be done to better understand facilitators’ training and support needs and their level of ease with implementing their roles in CoPs. Keywords: Teacher professional development; teacher continuous professional development; learning management systems; communities of practice; teacher learning circles An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Sierra Leone 2015 Population and Housing Census: Thematic Report on Disability - Kabia, Francis; Tarawally, Umaru (Statistics Sierra Leone, 2017)

Sierra Leone: Education Country Status Report: An analysis for further improving the quality, equity and efficiency of the education system in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2013)

National ICT Policy of Sierra Leone - Ministry of Information and Communications (Government of Sierra Leone, 2009)
Keywords: ⛔ No DOI found

Education Sector Plan, 2018-2020: Getting It Right – Service Delivery, Integrity and Learning in Sierra Leone - Ministry of Education, Science and Technology (Government of Sierra Leone, 2018)

Making strides to make digital literacy facilities accessible to children across Sierra Leone - Mason, Harriet (UNICEF Sierra Leone, 2022)
Making strides to make digital literacy facilities accessible to children across Sierra Leone

Building the Next Generation of Girls (and Boys) in Technology in Sierra Leone - Abakah, Julian; Mason, Harriet (UNICEF Sierra Leone, 2023)
Building the next generation of Girls (and boys) in Technology in Sierra Leone

Sierra Leone Demographic and Health Survey 2019 - Statistics Sierra Leone (The DHS Program, 2020)
ICF

The teacher salary system in Sierra Leone - Turrent, Victoria (2012)
Keywords: C:Sierra Leone; _C:Sierra Leone SLE; ⛔ No DOI found

The Agenda for Prosperity: Road to Middle Income Status - Government of Sierra Leone (2013)
Keywords: ⛔ No DOI found

Sierra Leone National Innovation and Digital Strategy (2019-2029). Digitization for all: Identity, Economy, and Governance - Directorate of Science, Technology & Innovation (Government of Sierra Leone, 2019)

Orange Education Portal - Orange Sierra Leone (2020)

Sierra Leone Education Sector Plan: Transforming learning for all 2022–2026 - Government of Sierra Leone (2022)

Sierra Leone Public Expenditure Review 2021: Fiscal Policy for a Sustainable Recovery - World Bank (World Bank, 2021)
This Fiscal and Debt Sustainability Note, the first module of a programmatic multisectoral Public Expenditure Review (PER), reviews the recent macro-fiscal challenges, analyzes their causes and consequences and provide policy options for enhancing the conduct of fiscal and PFM policies in the country. The first part of this module draws on the Boost database to provide a comprehensive overview of the budget covering both revenues and expenditures. It analyzes the composition of the budget (based on economic and functional classifications) and discusses the most critical PFM issues the country faces. It also assesses budget execution and the efficiency of public expenditure. The second part of the module focuses on fiscal risks and their implications for medium-term fiscal and debt sustainability. It examines the recent evolution of public debt, its main drivers and relationship to economic growth. It describes recent reforms to address fiscal and debt vulnerabilities and how these reforms have been affected by the global pandemic. It also analyzes the main fiscal risks with a focus on those stemming from State-Own Enterprises (SOEs), local councils, litigations, natural disasters, and health crises. This part uses simulations to analyze the most likely evolution of the public debt path over the next 20 years under alternative risk scenarios. Finally, the module proposes practical and actionable policy options to help improve the macro-fiscal environment over the short term and preserve debt sustainability over the medium term.
Keywords: Debt Sustainability; Fiscal Policy; Fiscal Sustainability; Public Debt; Public Expenditure; Public Financial Management; Public Investment Management; State-Owned Enterprises

Universal Access Development Fund | Home - Universal Access Development Fund (Sierra Leone) (2020)

Schools ICT project - Universal Access Development Fund (Sierra Leone) (2020)

Out-Of-School Children Study Sierra Leone - Government of Sierra Leone; Irish Aid; UNICEF (2021)

Scientists at DSTI go the extra mile to make it easier for children to get to school - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)
Mike Fabrikant, a software developer from Washington D.C., is embedded within the data science team at the Directorate of Science, Technology, and Innovation (DSTI) to support systems delivery. His workRead More

DSTI | Home - Directorate of Science, Technology & Innovation (Sierra Leone) (2020)

Ministry of Information and Communications | Home - Ministry of Information and Communications (Sierra Leone) (2020)

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Sierra Leone) (2018)

EMIS | Education Management Information System - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)

COVID-19 Education Emergency Response Plan - Ministry of Basic and Senior Secondary Education (Sierra Leone) (2020)

How the Government of Sierra Leone is improving its Education Data Hub - EdTech Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub, is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and […]
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

How the Government of Sierra Leone is improving its Education Data Hub (EdTech Hub, 2020)
Sierra Leone’s Education Data Hub is designed to make school-level data more useful in decision making. Nine months into its launch, MBSSE and DSTI were keen to understand who was using the Data Hub, the kinds of decisions it informed, and where improvements were needed to ensure that non-technical users, including policymakers, teachers, parents, and students could access and use…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Development Projects : Sierra Leone Free Education Project - P167897 - World Bank (World Bank, 2021)
Development Projects : Sierra Leone Free Education Project - P167897

Education Sector Plan 2018-2020 - Ministry of Education, Science and Technology (Sierra Leone) (2018)

Donor policies in post-war Sierra Leone - Kanyako, Vandy (Journal of Peacebuilding & Development, 2016)
The Sierra Leone peace process following the country's 1991–2002 civil war between the Government of Sierra Leone (GoSL) and the Revolutionary United Front (RUF) benefited immensely from the energetic involvement of an eclectic mix of donors. Traditional inter-governmental financial institutions and relatively new private funding foundations all channelled aid money and technical expertise through various multilateral and bilateral mechanisms for rebuilding the country. Without a doubt Sierra Leone's recovery from the debilitating 11-year war would not have come to pass in the time and manner it did without the robust intervention of such funders. Based on fieldwork conducted in Sierra Leone at the height of the peacebuilding process, this article outlines the role played by international donors in rebuilding post-war Sierra Leone. It posits that understanding the modus operandi of the assorted mix of donor agencies in creating the country's aid architecture is key to grasping the nuances of the Sierra Leone peace process. This is partly because the aid largesse, though well intentioned, was injected into a barely functioning system that lacked a coherent recipient regime. The article concludes that though donors were critical to Sierra Leone's rebuilding efforts, their lack of emphasis on a needs-centred funding mechanism created an inadequate model to address the country's complex post-war reconstruction challenges.

Districts of Teaching Excellence Sierra Leone - Beoku-Betts, Iman; Burgess, Flic (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Strengthening the use of data for decisions on teacher deployment in Sierra Leone: A Geospatial Approach to Workforce Allocation - McBurnie, Chris; Frazer, Madleen Madina; Dube, Gugulethu; Godwin, Katie (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Mapping the education data ecosystem in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Data-Driven Teacher Deployment in Sierra Leone: Practicalities and quantitative analysis of using a matching algorithm in the 2024/25 deployment cycle - Koutecký, Tomáš; Mackintosh, Alasdair; Huti, M; Adam, Taskeen; Godwin, Katie; Frazer, Madleen Madina (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko - SN Radio (2020)
#sierraleone #presidentbio #fatimabio #sierraleoneparliament #sierranetworkproduction #sierranetwork #sierranetworkwanpotshow President Bio Commissions Newly Constructed Dr Kadie Sesay Girls Secondary School In Port Loko. Latest News Website: http://www.blog.snradio.net FaceBook: http://www.facebook.com/SierraNetwork... Youtube: http://www.youtube.com/Salone2Bad Twitter: http://twitter.com/sierra_n_salone Radio: http://SNRadio.net Radio TuneIn App: http://tun.in/sfgyD SoundCould 1: http://www.soundcloud.com/sierra-network SoundCould 2: https://soundcloud.com/sierra-network-sl SoundCould 3: https://soundcloud.com/sierra-network... Contact Us: info@snradio.net Sierra Network For All That Matters Sierra Leone

Teacher Deployment in Sierra Leone Using a Geographic Information System-Supported Preference Matching Algorithm: A systems analysis - Anonymised for Peer Review (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Improving secondary education in Sierra Leone - De, Sourovi; Durrani, Zara; Khurshid, Ayesha (Oxford Policy Management, 2021)
We are leading the monitoring, evaluation and research delivery of a five year programme to improve secondary education and long term growth in Sierra Leone

National Education Policy - Ministry of Education, Youth and Sports (Sierra Leone) (2010)

Shifting Power Dynamics in Education Decision-Making: Investigating the role of a matching algorithm to improve teacher deployment in Sierra Leone - Godwin, Katie; Cameron, Emma; Frazer, Madleen Madina; Dube, Gugulethu; Mackintosh, Alisdair; Koutecký, Tomáš; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Education in Sierra Leone | Where We Work | Global Partnership for Education - Global Partnership for Education (2007)
Learn more about education in Sierra Leone, view grant information and education data, and explore the results and progress made by the country.

The Impact of GIS-Supported Teacher Allocation in Sierra Leone - EdTech Hub; Education Commission; Fab Inc. (EdTech Hub, 2022)
Keywords: HLR3; _r:AddedByZotZen

Digital School Census in 10 Weeks? How it was done in Sierra Leone - Namit, Kariba; Mai, Thanh Thi (World Bank Blogs, 2019)
Note: This blog is specifically about Sierra Leone’s successful transition to a digital school census but has broader implications for other countries who plan to adopt digital tools at a wider scale to collect data and monitor education and healthcare facilities in their countries. In April of last year, the new Minister of Finance of Sierra Leone approached the World Bank with a strong commitment to prioritize education and an intriguing request.

Sierra Leone Media Landscape Report - BBC Media Action (2018)

Advancing Data-Driven Decision-Making for School Improvement: Findings from the One Tablet Per School User Testing Programme in Sierra Leone - McBurnie, Chris; Beoku-Betts, Iman; Waistell, Daniel; Nallo, Michael (MBSSE, EdTech Hub, Leh Wi Lan, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

School Hits the Airwaves: Sierra Leone Turns to Education Radio as a Response to COVID-19 - World Bank (World Bank, 2021)
Sierra Leone's experience with education radio during the 2014 Ebola outbreak has helped strengthen its radio programming during school closures caused by the COVID-19 pandemic.

School Hits the Airwaves: Sierra Leone Turns to Education Radio as a Response to COVID-19 - World Bank (The World Bank, 2021)
Sierra Leone's experience with education radio during the 2014 Ebola outbreak has helped strengthen its radio programming during school closures caused by the COVID-19 pandemic.

Reconstructing education in post-conflict Sierra Leone - Pai, Grace (Security, Education and Development in Contemporary Africa, 2016)

Education in Emergencies Endline Evaluation Report – Sierra Leone - Sankoh, Didan; Cowan, Emma (Girls' Education Challenge, UK Aid, 2016)

Disability in and Around Urban Areas of Sierra Leone - Trani, Jean-Francois; Bah, Osman; Bailey, Nicki; Browne, Joyce; Groce, Nora; Kett, Maria (2017)

Project Information Document (PID): Sierra Leone Free Education Project (P167897) - World Bank (World Bank Group, 2019)

Sierra Leone research and knowledge systems: a rapid literature review - Tarawallie, Mamoud Idriss (INASP, 2015)

Using technology to improve the equity of teacher allocation in Sierra Leone: the challenge and a way forward - McBurnie, Chris; Vijil, Alejandra; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mitigating COVID-19 impacts and getting education systems up and running again: Lessons from Sierra Leone - Davis, Edward; Berry, Chris (Global Partnership for Education, 2020)
Reflexions on some of the lessons from the Sierra Leone Ebola education response that could be relevant for countries facing shutdowns of their education systems due to the COVID-19 pandemic.

What Matters Most for Teacher Deployment? A case study of teacher preferences in Sierra Leone - McBurnie, Chris; Godwin, Katie; Beoku-Betts, Iman; Bernard-Jones, Lydia; Haßler, Björn (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _C:Sierra Leone SLE; _r:AddedByZotZen

Digital 2023: Sierra Leone - Kemp, Simon (DataReportal – Global Digital Insights, 2023)
All the data, insights, and trends you need to help you make sense of the “state of digital” in Sierra Leone in 2023, including detailed statistics for internet use, social media use, and mobile use, as well as user numbers for all the top social platforms.

‘Digital Her’ conference calls time on the gender-gap in Sierra Leone’s digital boom - Forna, Memuna (2024)
The tech sector is growing faster in Africa than any other region. The Digital Her Conference (21 March 2024) asks how can we ensure Sierra Leonean women share fully in the opportunities facilitated by the digital economy as creators, consumers and beneficiaries? Sierra Leone is on the brink of a tr

Developing Inclusive Education Policy in Sierra Leone: A Research Informed Approach - Rose, R.; Garner, P.; Farrow, B. (Inclusion, Equity and Access for Individuals with Disabilities., 2019)

Open Data Readiness Assessment: Prepared for the Government of Sierra Leone - Chrzanowski, Pierre; Holm, Jeanne; Manley, Laura; Dodds, Elizabeth; Baker, Rob (World Bank Group; Open Aid Partnership, 2016)

RECOVR Sierra Leone: Tracking the Effects of the COVID-19 Pandemic - Warren, Shana; Parkerson, Doug; Collins, Elliott (Innovations for Poverty Action, 2020)

Republic of Sierra Leone Higher and Tertiary Education Sector Policy Note - World Bank (2013)

Education service transformation in Sierra Leone: Where policy meets the people - Sengeh, David (2020)

Successes and challenges of implementing a teacher education project in rural Sierra Leone - Mcdermott, Peter; Allen, Nancy (International Journal of Educational Research, 2015)

TVET and community reintegration: exploring the connections in Sierra Leone's DDR process - Paulson, J. (International handbook of education for the changing world of work: bridging academic and vocational learning, 2009)

Devising New Models for School Improvement in Developing Nations: Sierra Leone, a case study - Mason, Miriam Theresa (Durham University, 2019)

Using technology to support teacher continuous professional development in Sierra Leone - Beoku-Betts, Iman; Plaut, Daniel; Tanweer, Rabia; Tanweer, Iman Beoku-Betts, Daniel Plaut and Rabia (EdTech Hub, 2022)
In Sierra Leone, EdTech Hub has been working closely with the TSC and the World Bank over the last 18 months to design a TCPD model that will provide primary school teachers with tools to improve their literacy and numeracy instruction.

A Skills Gap Analysis for Private Sector Development in Sierra Leone 2012 Economic Sector Work - Mannah, Emmanuel; Ngadi Gibril, Yvonne (2012)

Sierra Leone | Education and Literacy Statistics - UNESCO (2020)
...

GSMA Mobile Connectivity Index | Sierra Leone - GSMA (2018)
The GSMA Mobile Connectivity Index is a global mobile connectivity and digital economy guide covering 150 countries and 7 sub-regions

Sierra Leone Multiple Indicator Cluster Survey - UNICEF (2017)

COL in the Commonwealth: Sierra Leone - Commonwealth of Learning (2020)

Using examination and learning assessment data to uncover foundational skill gaps in Sierra Leone’s secondary schools - Waistell, Daniel; De, Sourovi; Ofori Owusu, Diana; Allen, Reg; Sanni, Kayode; Dupigny, Albert (UKFIET Conference, 2019)
Keywords: ⛔ No DOI found

The Athens of West Africa: A History of International Education at Fourah Bay College, Freetown, Sierra Leone - Paracka, Daniel J. (2006)
This book is about Fourah Bay College (FBC) and its role as an institution of higher learning in both its African and international context. The study traces the College's development through periods of missionary education (1816-1876), colonial education (1876-1938), and development education (1938-2001).

Sierra Leone: Transforming the Country through Innovation - O'Connor, Shane; Zurutuza, Naroa (UNICEF, 2019)

Project Information Document: Sierra Leone Free Education Project - World Bank (2019)

Revitalizing Education Development in Sierra Leone (REDISL) Project - World Bank (2014)

It takes a village to raise a teacher: the Learning Assistant programme in Sierra Leone - Crisp, Martin; Wolfenden, Freda (2017)

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Wright, Dr. Cream (Global Partnership for Education; World Bank, 2018)

How Sierra Leone is betting on data to fight the impact of climate change on schools - Momoh, A; Atherton, Paul (Global Partnership for Education, 2022)
Data can significantly improve decision-making and allow for prioritizing interventions to benefit the most vulnerable populations. That’s why the ministry of Education in Sierra Leone is working with Fab Inc. to develop a web-based data tool that helps estimate and prioritize where new schools are really needed.

Ebola, Education And Innovation In Sierra Leone - Berry, Chris (DFID bloggers, 2015)
Keywords: ___working_potential_duplicate

How can Sierra Leone’s education response after Ebola help with the COVID-19 response? - Bangay, Colin (The Education and Development Forum (UKFIET), 2020)
This blog is written by Colin Bangay, Senior Education Adviser, Department for International Development (DFID). It aims to look at some practical and sensible lessons from the education response in Sierra Leone during the Ebola outbreak, to help others as they face closures of education systems. This blog was originally published on the Global Partnership […]

Introduction of an EdTech intervention to support learning of foundational skills in Sierra Leone: policy, teacher, and community perspectives - Lurvink, Anne-Fleur; Pitchford, Nicola J. (Frontiers in Education, 2023)
Background: Like many other countries, Sierra Leone faces significant challenges with primary education resulting in many children leaving primary school without acquiring basic foundational skills. To address these challenges, an educational technology (EdTech) intervention was implemented in 20 primary schools located in two marginalized districts in Sierra Leone. While this EdTech intervention has been shown to raise learning outcomes, little is known about the impacts on the broader education ecosystem. This paper investigates how this EdTech intervention might address some the challenges faced with primary education in Sierra Leone, by examining policy, teacher, and community perspectives. Method: A mixed methods approach was employed which included a policy mapping exercise, a survey of teachers training needs in supporting the development of foundational skills with grade 1 learners, an interview with teachers after they had delivered the EdTech intervention to garner their perceptions and experiences of using the technology in their class, and focus groups with teachers and other community members to gain insights into how the EdTech intervention had been received. Results: Findings from the policy mapping exercise and quantitative data from the survey of teacher training needs were triangulated with qualitative data from the interviews and focus groups. Four key themes emerged relating to the effective and sustained use of this EdTech intervention to support the acquisition of foundational skills by primary school children in Sierra Leone: (1) the need for continued teacher professional development, (2) the use of English as the language of instruction, (3) access to the technology by children with special educational needs and disabilities (SEND), and (4) the importance of active community engagement in supporting the intervention. Discussion: Collectively, results indicated that the EdTech intervention employed in this study aligned well to the education policy in Sierra Leone. Enhanced teacher training is needed, especially in using English as the language of instruction, and continued community engagement is essential for scaling the intervention effectively and ensuring that all children, including those with SEND, access the technology at primary school. These results have implications for other EdTech intervention deployed in resource-poor settings to enhance learning of foundational skills.

Final Evaluation of the Project: Increasing Access, Retention and Performance in Primary Education: Implemented by Child to Child & the Pikin-To-Pikin Movement Kailahun District, Sierra Leone, 2011-2016 - Institute for Development (2016)

‘Tich Mi Ar Tich Dem’: Designing a low-cost and scalable teacher professional development in Sierra Leone - Walker, Hannah; Tegha, Ghislaine; Lurvink, Anne-Fleur; McBurnie, Chris (Open Development & Education, 2022)
Reading Time: 4 minutes Over the past two decades, Sierra Leone has faced a series of shocks: a civil war, landslides, Ebola, and the COVID-19 pandemic. These shocks have aggravated the learning crisis that the country’s education system faces—and dramatically increased the pressure on teachers to deliver high-quality support to children. In this context, the Ministry of Basic and […]

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (Education continuity during the Coronavirus crisis, 2020)

Education Needs Assessment Report - Sierra Leone - Plan International (2016)

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
Keywords: ___working_potential_duplicate

2021 Annual School Census Final Report - Ministry of Basic and Senior Secondary Education, Sierra Leone (2022)

Republic of Sierra Leone Settlement Extents - GRID3 (Center for International Earth Science Information Network (CIESIN), Columbia University and Novel-T, 2021)

Are LLMs useful in the poorest schools? TheTeacher.AI in Sierra Leone - Choi, Jun Ho; Garrod, Oliver; Atherton, Paul; Joyce-Gibbons, Andrew; Mason-Sesay, Miriam; Björkegren, Daniel (arXiv, 2024)
Education systems in developing countries have few resources to serve large, poor populations. How might generative AI integrate into classrooms? This paper introduces an AI chatbot designed to assist teachers in Sierra Leone with professional development to improve their instruction. We describe initial findings from early implementation across 122 schools and 193 teachers, and analyze its use with qualitative observations and by analyzing queries. Teachers use the system for lesson planning, classroom management, and subject matter. Usage is sustained over the school year, and a subset of teachers use the system more regularly. We draw conclusions from these findings about how generative AI systems can be integrated into school systems in low income countries.
Keywords: Computer Science - Computers and Society

Education Sector Analysis. Assessing the enabling environment for gender equality - Republic of Sierra Leone (UNICEF, IIEP - UNESCO, 2020)

Technology and Teacher Professional Development (TPD): the Process and Content of Microlearning in a School-Based Integrated In-Service Teacher Education (INSET) Project - Junaid, Muhammad Ibn; Ogange, Betty; Allela, Melisa (Commonwealth of Learning (COL), 2019)
Continuing teacher professional development for all teachers across the entire school system poses a challenge in many contexts, especially in developing countries. Teachers from schools located in remote rural areas usually have fewer professional development opportunities due to the lack of accessibility either to their schools or to professional development resources. On-site school-based professional development is a viable option if innovative design is adapted to generate microlearning resources that teachers can easily access and share. This paper reports on a technology enabled school-based integrated INSET project coordinated by the Freetown Teachers College (FTC) in 12 junior secondary schools (JSS) in Sierra Leone under the COL’s Teacher Futures Programme. The project represents an innovation in TPD and is different from the general type of face-to-face and exclusively paper-based in-service teacher training programme common in Sierra Leone. Under the new project a multimodal approach is used where the FTC mentors and the communities of learners (JSS teachers) are presented with both print and microlearning resources and also provided access to an eLearning platform and the use of mobile phones as the main vehicles of delivery. Microlearning is an emergent learning strategy known for its quick response in bridging skills and knowledge gaps. In the context of the INSET Project, it involves a weekly dose of pedagogical content knowledge and skills, including modelling of classroom best practices which teachers can adapt and use. The project design and methods are briefly described, but the main focus of the paper is on the microlearning component of this project and discusses the use of mobile technology in the delivery and implementation of TPD in the 12 project schools. The emphasis is on the methodological and management challenges that arise in creating and nurturing communities of practice (CoPs) in a school-based setting and how these are addressed by the various schools involved.

Teachers and Teaching in Sierra Leone - The World Bank (2021)

How Can Participatory Methods Centre Teachers Within Education Policy? - Koomar, Saalim (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at the potential for participatory methods to bring teachers closer to the decision-making table. Insights from those closest to the work shed light on the daily contextual realities that can determine the mechanisms for optimal success or failure of a programme. However, these voices are often neglected in the design, implementation, and evaluation of interventions. We examine why and how teachers can have a voice and a space to share their wisdom to inform and improve education policy. We draw on EdTech Hub's work across various low- and middle-income contexts to offer practical insights when using or planning to use participatory methods. We share details of some of the most significant findings and engaging lessons EdTech Hub has learnt about the methods used and how they have contributed to ensuring teachers’ voices are heard at the policymaking level. We also explore areas that require further research, noting five issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to participatory methods for centring teachers in education policy. Keywords: teacher; participatory methods; action research; implementation research; teacher professional development; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

2019 Annual Schools Census Report And Statistical Abstract - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2019)

Benefit Incidence Analysis of the Education Sector in Sierra Leone - Ministry of Finance (Government of Sierra Leone, 2023)
DOWNLOAD

The Future of EMIS: A Public Financial Management Perspective - Cresswell, Simon; Long, Cathal; Fraser, Alasdair (EdTech Hub, 2023)
Policymakers in low- and lower-middle-income countries are in a bind: while more complex EMIS designs may make processes more likely to fail following donor exit, simple EMIS designs do not provide enough information to track the effects of reforms and progress addressing the learning crisis. Even for basic measures, EMIS appear to generate inaccurate data in many cases. Reflections on EMIS implementation challenges point to demand and supply issues, with the former being the more important determinant for realising EMIS potential and their ongoing development. This paper considers demand and supply for EMIS from a public financial management (PFM) perspective. Keywords: public financial management, budgeting, digital, data governance, education An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

FQSE – Free Quality School Education - Ministry of Basic and Senior Secondary Education Sierra Leone (Ministry of Basic and Senior Secondary Education Sierra Leone, Government of Sierra Leone, 2018)

Sierra Leone Teaching Service Commission Act - Government of Sierra Leone (2011)

About Us | Teaching Service Commission - Sierra Leone - Teaching Service Commission (Government of Sierra Leone, 2020)

Sierra Leone Education Sector Plan 2022-2026 - Ministry of Basic and Senior Secondary Education; Ministry of Technical & Higher Education (Government of Sierra Leone, 2022)

National Strategy for Out-of-School Children in Sierra Leone - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2022)

Radio: A Rapid Evidence Review - Damani, Kalifa; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of the existing literature on the use of radio in education in low- and middle-income countries (LMICs). The present RER has been produced in response to the novel 2019 coronavirus (COVID-19), and the resulting widespread shutdown of schools. It, therefore, highlights transferable insights that may be applicable to educational responses resulting from the limitations caused by COVID-19. Established approaches to delivering distance education have renewed salience during this period because many students cannot access schooling in a school building due to social distancing requirements. As one of the longest-serving and most accessible types of educational technology (EdTech), and one that has had some success in education delivery in an LMIC context that was affected by an epidemic, it is particularly useful to focus on radio (Barnett et al., 2018; Hallgarten, 2020). Notably, the RER aims neither to advocate nor discourage the use of radio in education in response to the COVID-19 pandemic. Instead, it provides an accessible summary of existing evidence on the topic so that educators, policy makers and donors might make informed decisions about the potential of radio in education delivery.
Keywords: L:English UXZJW5DR; TAG:E:Primary education QIVZD2B2; TAG:E:Secondary education JS5BG2RE; TAG:F:Access W8TZWAGE; TAG:F:Educational data QWBAFGFR; TAG:F:Online and distance teaching and learning A32ARSFK; TAG:H:Audio and Radio QIAXGMEU; TAG:P:Teachers DAJFZBM8; TAG:W:Low connectivity and/or electricity KET3PKDI; _DOILIVE; _EdTechHub_Output; _GS:indexed; _L:English UXZJW5DR; _MELA_seen; _T:E:Primary education QIVZD2B2; _T:E:Secondary education JS5BG2RE; _T:F:Access W8TZWAGE; _T:F:Educational data QWBAFGFR; _T:F:Online and distance teaching and learning A32ARSFK; _T:H:Audio and Radio QIAXGMEU; _T:P:Teachers DAJFZBM8; _T:W:Low connectivity and/or electricity KET3PKDI; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Basic and Senior Secondary Education Act, 2023 - Government of Sierra Leone (2023)

EMIS – MBSSE - Government of Sierra Leone (2022)

Exploring donor-driven skills development as a channel of continued aid dependency - Harris, Jamelia (Third World Quarterly, 2023)
Keywords: NGOs; Sierra Leone; Skills development; aid; dependency

Education Sector Analysis: Assessing the enabling environment for gender equality - Republic of Sierra Leone; UNICEF; IIEP-UNESCO Dakar (2020)

A rapid scan of the EdTech landscape in 11 countries - Taddese, Abeba (EdTech Hub, 2020)
By Abeba Taddese We have just produced rapid scans of the EdTech landscape in 11 countries: Ghana, Jordan, Kenya, Liberia, Nigeria, Pakistan, Rwanda, Senegal, Sierra Leone, Tanzania, and Zimbabwe. The scans are based primarily on desk research and offer a glimpse into the countries’ EdTech ecosystems. They examine enabling factors for EdTech from a holistic systems perspective but are by…
Keywords: _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech for Education in Emergencies: A Rapid Evidence Review - Barnes, Katrina; Ramesh Vasudevan, Sharanya; Flam, Rebekka (EdTech Hub, 2025)
This Rapid Evidence Review (RER) provides a synthesis of recent evidence relating to the implementation of EdTech programmes, platforms, and devices in emergency contexts. The main aim of the review is to provide education decision-makers, funders, and implementers (among others) with a clear picture of ‘what works’ regarding EdTech in emergencies. Crucially, it also aims to create an understanding of the conditions necessary to ensure the effectiveness of these interventions. Accordingly, the results of the review are grouped under three key themes: types of EdTech that are most effective in emergencies; barriers and challenges that limit EdTech effectiveness in emergencies; and conditions for effective implementation of EdTech in emergencies. Keywords: Education in Emergencies; EdTech; crisis contexts; remote learning An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Education in Africa: What Are We Learning? - Evans, David; Acosta, Amina Mendez (2020)
Countries across Africa continue to face major challenges in education. In this review, we examine 145 recent empirical studies (from 2014 onward) on how to increase access to and improve the quality of education across the continent, specifically examining how these studies update previous research findings. We find that 64 percent of the studies evaluate government implemented programs, 36 percent include detailed cost analysis, and 35 percent evaluate multiple treatment arms. We identify several areas where new studies provide rigorous evidence on topics that do not figure prominently in earlier evidence syntheses. New evidence shows promising impacts of structured pedagogy interventions (which typically provide a variety of inputs, such as lesson plans and training for teachers together with new materials for students) and of mother tongue instruction interventions, as well as from a range of teacher programs, including both remunerative (pay-for-performance of various designs) and non-remunerative (coaching and certain types of training) programs. School feeding delivers gains in both access and learning. New studies also show long-term positive impacts of eliminating school fees for primary school and positive impacts of eliminating fees in secondary school. Education technology interventions have decidedly mixed impacts, as do school grant programs and programs providing individual learning inputs (e.g., uniforms or textbooks).
Keywords: ⛔ No DOI found

The Education Act, 2004 - Kabbah, President Alhaji Ahmad Tejan (2004)

Keynote Address by His Excellency President Julius Maada Bio on the theme of: "Education for Development" at the launch of the Free Quality School Education Programme - Maada Bio, Julius (2018)

What makes a good classroom? New UIS data on school conditions - UNESCO (UNESCO, 2019)
New data from the UNESCO Institute for Statistics (UIS) reveal serious disparities in the schooling conditions facing children and teachers – from access to electricity, clean drinking water and single sex-toilets to Internet access and computers. Classroom conditions are key in providing a quality education for all. For children who struggle to enrol in school, for example due to poverty or discrimination on the grounds of gender or disability, poor school conditions can further undermine their chances of a quality education. What are the new data looking at?

The Tertiary Education Commission Act - Kabbah, President Alhaji Ahmad Tejan (2001)

The National Council for Technical , Vocational and other Academic Awards Act - Kabbah, President Alhaji Ahmad Tejan (2001)

The Polytechnics Act - Kabbah, President Alhaji Ahmad Tejan (2001)

The Universities Act - Kabbah, President Alhaji Ahmad Tejan (2005)

Continental Education Strategy For Africa (2016 – 2025) - African Union (2016)

Education for sustainable development in Africa: a critique of regional agendas - Tikly, Leon (Asia Pacific Education Review, 2019)
Education is often perceived in policy agendas as playing a transformative role in realising sustainable development and the SDGs on the continent. The assumption is based, however, on an insufficiently critical understanding of the historical role of education in supporting unsustainable development. The article provides a critical account of the relationship between education policy and sustainable development in Africa as an aspect of the postcolonial condition, i.e. as an aspect of the colonial legacy and of Africa’s position in relation to contemporary processes of globalisation. It is argued that if education is to play a transformative role in relation to sustainable development then education policy needs to be fundamentally re-oriented and harnessed to wider processes of economic, cultural and political transformation in the interests of social and environmental justice.

Rwanda Vision 2020 - Ministry of Finance and Economic Planning (Republic of Rwanda, 2000)

Kenya Vision 2030: A Globally Competitive and Prosperous Kenya - Government of Kenya (Republic of Kenya, 2007)

Ethiopia Growth and Transformation Plan II (GTP II) | Green Growth Knowledge Platform - Ethiopia National Planning Commission (Federal Democratic Republic of Ethiopia, 2016)

DSTI Education Data Hub - DSTI (2020)

Education Innovation Challenge - Reflection & Learning Summit Report - DSTI (2020)

Reimagining Education for Continuous Learning and Teaching - Sengeh, Hon Minister David Moinina; Team, MBSSE Delivery; Team, Hon Minister David Moinina Sengeh and MBSSE Delivery (EdTech Hub, 2021)
EdTech Hub has partnered with the Ministry of Basic and Senior Secondary Education in Sierra Leone to increase the use of evidence in decisions around EdTech. Click to read more.

Radical inclusion means teaching children in a language they understand - Bah, Chernor (Brookings, 2022)
Chenor Bah examines how Sierra Leone is trying to incorporate radical inclusion within the national education system by ensuring children are taught their mother-tongue for the first three to five years of schooling.

Sierra Leone Series: Plan International and the importance of community support for distance teacher professional development programmes - McBurnie, Chris; Saidu, Arthur; Rincon Casado, Eusebio; Shergill, Maggie (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:analysis:nopdf; _r:AddedByZotZen

Sierra Leone Series: the Pikin-to-Pikin Movement and its focus on child protection, education, nutrition and health - McBurnie, Chris; Swaray, Abdulai; Kamara, Bai (EdTech Hub, 2021)
Keywords: _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _r:AddedByZotZen

From algorithm outputs to classroom impact: A conversation with Marian Abu, director of teacher management at the Teaching Service Commission - Frazer, Madleen Madina (EdTech Hub, 2024)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _EdTechHub_Output; _r:AddedByMyEducationEvidence

UNICEF Sierra Leone - UNICEF (2022)
Learn how we are supporting children across the country to reach their full potential.

Sierra Leone – Giga - GIGA; UNICEF (2023)

Sierra Leone population 2020 - WorldPop (2018)
RF-based gridded population distribution datasets produced in the framework of the Global Project - Funded by The Bill and Melinda Gates Foundation (OPP1134076)
Keywords: Population distribution, Population, Dasymetric disaggregation

Transforming Teacher Deployment: Lessons from a matching algorithm tool - Frazer, Madleen Madina; Adam, Taskeen; Godwin, Katie; Mackintosh, Alisdair; Haßler, Björn (EdTech Hub, 2025)
An output of the EdTech Hub, https://edtechhub.org/
Keywords: _comingsoon; _r:AddedByMyEducationEvidence

Sierra Leone | Technology | Education Profiles - UNESCO (UNESCO, 2023)

EAGER Scenario Model – Sierra Leone - Cochran, Mikaela (The International Rescue Committee, 2022)

Sierra Leone Free Education Project - World Bank (2020)

Education | Sierra Leone | Save the Children - Save the Children (2024)

Open Data Readiness Assessment: Sierra Leone - World Bank (2015)

Education Workforce Management in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)

Sierra Leone Education Attendance Monitoring System - Teaching Service Commission (2020)

Country-level research review: Sierra Leone - Kallon Kelly, Christiana; Koomar, Saalim; Kreimeia, Adam; McBurnie, Chris; Mitchell, Joel; Myers, Christina (2020)
Keywords: dode_eth-src-eth

Teacher Management Policy for Sierra Leone - Teaching Service Commission (2020)
Keywords: _C:Sierra Leone SLE

Government of Sierra Leone Education Data Hub - Directorate of Science, Technology and Innovation (2019)

Education Workforce Spatial Analysis in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Commission, 2020)
Keywords: _yl:a; ⛔ No DOI found

Sierra Leone - Multiple Indicator Cluster Survey 2017 - World Bank (2017)

Cost-Effective Approaches to Improve Global Learning - Global Education Evidence Advisory Panel (2023)

Education for Development - Maada Bio, Julius (2018)

Proportion of schools with access to basic facilities, all schools - UNESCO (2018)

SALCAB | Home - SALCAB (2020)

Mobile Learning Lab Evaluation & Analysis - 60 Million Girls (60 million girls, 2018)

Education Workforce Recruitment and Matching in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (Education Workforce Initiative, 2020)
Keywords: _yl:b; ⛔ No DOI found

Individuals using the Internet (% of population) - Sierra Leone - International Telecommunication Union (World Bank Open Data, 2022)
Free and open access to global development data

Education Workforce Supply and Needs in Sierra Leone - Mackintosh, Alasdair; Ramirez, Ana; Atherton, Paul; Collis, Victoria; Mason-Sesay, Miriam; Bart-Williams, Claudius (the Education Commission; Fab Inc., 2020)
Keywords: ⛔ No DOI found

EdTech, Learning and Equity: The EdTech Hub Research Portfolio - Haßler, Björn; Wagner, Dan; Outhwaite, Laura (EdTechHub, 2023)
Keywords: _internal; _r:AddedByMyEducationEvidence

Sierra Leone teacher & school MIS developments: Sierra Leone Education Attendance Monitoring System (SLEAMS) and Teacher Records Management (TRM) system - Graham, Hannah (2021)

Teaching and Testing by Phone in a Pandemic - Crawfurd, Lee; Evans, David K.; Hares, Susannah; Sandefur, Justin (Center for Global Development, 2021)
How did children learn while schools were closed during 2020 due to the COVID-19 pandemic? In this paper we evaluate the effectiveness of live tutoring calls from teachers, using a randomized controlled trial with 4,399 primary school students in Sierra Leone.
Keywords: ___working_potential_duplicate

Wi De Ya, One Tablet Per School, Sierra Leone - CGA Technologies (2023)

Sierra Leone Secondary Education Improvement Programme II (SSEIP II) - Foreign, Commonwealth Development Office (GOV.UK, 2022)

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - Foreign, Commonwealth Development Office (GOV.UK, 2024)

Sierra Leone joins Elon Musk's Starlink satellite service - Komminoth, Leo (African Business, 2023)
The country now joins Nigeria, Mozambique, Rwanda, and Mauritius as African nations connected to Elon Musk's Starlink.

Leh Wi Learn - Sierra Leone Secondary Education Improvement Programme - DFID (2018)

Sierra Leone and Liberia: Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (2020)

Systems-Level Analysis of Education Service Delivery in Sierra Leone - Education Partnerships Group (2020)

Sierra Leone: Economic Development Documents-National Development Plan, 2019-23 - International Monetary Fund (IMF, African Department, 2019)

Innovative Education Workforce Analysis for More Equitable Education: Sierra Leone - Education Workforce Initiative (Education Commission, 2020)

Independent Reporting Mechanism (IRM): Sierra Leone Design Report 2019–2021 - Field, Tracey-Lynn (Open Government Partnership, 2020)

Sierra Leone Education Attendance Monitoring System (SLEAMS) Final Technical Report - Graham, Hannah; Kawa, Muniru; Lee, Philip; Malyon, Stephanie; Hayward, Harry; Conteh, Sheriff; Chandia, Gloria (Charlie Goldsmiths Associates, 2020)

West African Senior School Certificate Examination: Sierra Leone Results Analysis - Ministry of Basic and Secondary Education (2022)

Automated teller machines (ATMs) (per 100,000 adults) - Sierra Leone - World Bank (2012)

Teachers and the Teaching Profession in Sierra Leone: A comprehensive situation analysis - Wright, Cream (Teaching Service Commission, 2017)

A longitudinal study of learning, progression, and personal growth in Sierra Leone - Johnson, David; Hsieh, Jenny (University of Oxford, 2019)

Open Government Case Study: Costing Sierra Leone’s Open Data Program - Joswiak, Naomi (Results for Development, 2017)
Keywords: ___working_potential_duplicate

Sierra Leone Education Attendance Monitoring System (SLEAMS) Pilot Phase: Inception Report - Kawa, Muniru; Graham, Hannah; Lee, Philip; Murray, Tobias; Malyon, Stephanie (Charlie Goldsmiths Associates, 2020)

Teachers and Teaching in Sierra Leone : Teacher Quality and Management Study - World Bank (2021)
Keywords: _C:Sierra Leone

Incidence of HIV, all (per 1,000 uninfected population) - Sierra Leone | Data - World Bank (2020)

Guidance Note on Education Data Mapping in Sub-Saharan Africa: Moving from theory to practice - Selwaness, Irene; Adam, Taskeen; Lawson, Laté; Heady, Lucy (EdTech Hub, 2022)
Keywords: _r:AddedByZotZen

Republic of Sierra Leone: Education sector analysis: assessing the enabling environment for gender equality - UNICEF (2020)

The permanent input hypothesis : the case of textbooks and (no) student learning in Sierra Leone - Sabarwal, Shwetlena; Evans, David K.; Marshak, Anastasia (Policy research working paper : WPS, 2014)

Education continuity during the Coronavirus crisis: Sierra Leone and Liberia Rising Academy Network on air - Lamba, Keya; Reimers, Fernando (Rising Academy Network, 2020)

Getting girls back into school: strategies for successfully re-enrolling girls in Ghana and Sierra Leone - Belfield, Sophie; Mathur, Meenu; Caine, Ellie (FCDO - GEC, 2021)

Live tutoring calls did not improve learning during the COVID-19 pandemic in Sierra Leone - Crawfurd, Lee; Evans, David K.; Hares, Susannah; Sandefur, Justin (Journal of Development Economics, 2023)

Sierra Leone Case Study: Review of Technology-Based Interventions to Address Child Marriage and Female Genital Mutilation - Data-Pop Alliance; United Nations Population Fund; UNICEF (2023)

Mapping education data in sub-Saharan Africa: Our experience from the Unlocking Data campaign and Sierra Leone - Unlocking Data (2021)

Navigating the ‘Data Revolution’: A Case Study on the One Tablet Per School Programme in Sierra Leone - McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode

Recovering from school closures in Sierra Leone: Status of pupil learning outcomes in junior and senior secondary schools - Leh Wi Lan (2021)

Incidence of malaria (per 1,000 population at risk) - Sierra Leone, Sub-Saharan Africa (excluding high income) | Data - World Bank (2018)

How Can EMIS be Designed and Implemented in Ways That Make Them Used and Useful? - Adam, Taskeen; Mitchell, Joel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at education management information systems (EMIS). EMIS are pivotal in educational administration, facilitating the digitisation of processes and data to enable informed decision-making. However, persistent challenges impede their effectiveness. We examine why it is vital to consider how EMIS are designed and implemented, particularly with regard to the needs and contexts of low- and middle-income countries (LMICs). We consider constraints in technical capacity, limited funding, and insufficient user engagement. We identify concrete, evidence-based recommendations for how to make EMIS useful and used more frequently based on current and recent research. To enhance EMIS efficacy, there is a need to underscore utility and usability, ensuring the collection of pertinent data and user-friendly interfaces. Furthermore, the social implications of EMIS data on individuals and communities must be considered in order to meet their needs. We also explore areas for further consideration and include lists of resources relevant to EMIS and questions and solutions to consider. Keywords: education management information systems (EMIS); low- and middle-income countries (LMICs); user-centred design; evidence-based decision-making; EdTech; educational administration. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence; _r:AddedByZotZen

Tech plus teachers: Did one-on-one phone tutorials help kids learn better during school closures in Sierra Leone? - Crawfurd, L; Evans, D; Guiterrez Bernal, M; Hares, S; Sam-Kpakra, R; Sandefur, J; Shojo, M (2021)

Toward a holistic approach to EdTech effectiveness: Lessons from Covid-19 research in Bangladesh, Ghana, Kenya, Pakistan, and Sierra Leone - Nicolai, Susan; Jordan, Katy; Adam, Taskeen; Kaye, Tom; Myers, Christina (International Journal of Educational Development, 2023)

A Comprehensive Situation Analysis of Teachers and the Teaching Profession in Sierra Leone: Final report presented to the Teaching Service Commission - Teaching Service Commission (Global Partnership for Education, 2018)

No Teacher is an Island: A case study on the enablers and barriers for effective school-based teacher professional development in Sierra Leone - Lurvink, Anne-Fleur; Bangura, Zainab; Fortune, Alhaji; George, Alex H.; Godwin, Katie; Mason-Sesay, Miriam; Moseray, David; Tholley, Ibrahim; Turay, Emmanuel B.; Haßler, Björn; Open Development & Education (OpenDevEd, 2022)

Cost Effective Approaches to Improve Global Learning What Does Recent Evidence Tell Us Are Smart Buys for Improving Learning in Low-and-Middle-Income Countries - Global Education Evidence Advisory Panel (World Bank; FCDO; Building Evidence in Education, 2020)

Understanding the Barriers and enablers of Effective Communities of Practice in Sierra Leone Through a Collaboration Between Dubai Cares and Open Development and Education - Lurvink, Anne-Fleur (Open Development & Education, 2019)

Back-to-School Campaigns Following Disruptions to Education - Chuang, Rachel; Kaye, Tom; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
This EdTech Hub Helpdesk response focuses on back-to-school campaigns following disruptions to education, ensuring that children rapidly return to school as soon as it is safe and practical. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Ed-Tech landscape and challenges in Sub-Saharan Africa - Adeniran, Adedeji; Adedeji, Abdulfatai; Nwosu, Emmanuel; Nwugo, Emmanuel; Nnamani, Great (Southern Voice, 2023)
This study examines the adoption of education technology (ed-tech) in primary and secondary education in 10 sub-Saharan African countries: Nigeria, South Africa, Sierra Leone, Uganda, Kenya, Tanzania, Cameroon, Benin, Malawi, and Senegal. The study assesses the development and implementation of ed-tech policies and programmes in the region, exploring how far ed-tech has advanced learning outcomes, improved access, and reduced education inequalities within and between countries in sub-Saharan Africa.

The use of 'building blocks' to develop digital platforms for education in sub-Saharan Africa - Adam, Taskeen; El-Serafy, Yomna; Podea, Marius; Haßler, Björn (EdTech Hub, 2021)
We set out to investigate the existing and potential use cases of open-source, modular ‘building blocks’ to build digital platforms for education in sub-Saharan Africa (SSA). Building blocks fall into two main categories: teaching and learning (e.g., learning management systems) and education system management (e.g., data collection tools).
Keywords: _EdTechHub_Output; _MELA_seen

How Can Implementers Apply Digital Personalised Learning in Schools? - Plaut, Daniel (EdTech Hub, 2024)
This Learning Brief is part of the EdTech Hub Learning Brief Series, providing practical resources for people working to improve the use of technology in education. In this brief, we look at digital personalised learning (DPL), a promising EdTech approach to improving learning outcomes, and consider how to implement this approach in school settings. We draw on work from EdTech Hub and other prominent researchers to first unpack the ‘basics’ of DPL implementation. These include the importance of teaching at the right level as a driver of DPL’s impact, and how DPL tools are applied in schools as supplementary learning and / or integrated into existing curricula. We also consider some of DPL’s technical requirements and achievements in improving learning outcomes. We then explore emerging insights about effective DPL implementation in schools, including the role of teachers as facilitators, the evidence behind student-device ratios, and the importance of coordinating DPL implementation with broader education system actors. Lastly, we look at areas that require further research, noting issues that we at EdTech Hub are still grappling with in our own work, and include lists of resources relevant to DPL application in education systems. Keywords: digital personalised learning; DPL; implementation research; teaching at the right level; learning outcomes; education policy An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How to Guide: Delivering High-Quality Radio Learning - Rising Academies; EdTech Hub (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH

Bangladesh Back-to-School Campaign - Kaye, Tom; Chuang, Rachel; Moss Coflan, Caitlin; Haßler, Björn (EdTech Hub, 2020)
The EdTech Hub received a request from the FCDO Bangladesh team to provide a topic brief identifying best practices from previous back-to-school campaigns following disruptions. Key themes of effective school re-openings are examined in the context of modalities used to deliver distance learning (e.g., radio, television).
Keywords: C:Bangladesh; COV:COVID and reopening of schools; E:Pedagogy; E:Teacher education (pre-service and in-service); F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _yl:g; _zenodo:submitted; _zenodoETH; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Dialling up Learning: Testing the Impact of Delivering Educational Content via Interactive Voice Response to Students and Teachers in Ghana - Afoakwah, Edmund; Carballo, Francisco; Caro, Alex; D’Cunha, Samantha; Dobrowolski, Stephanie; Fallon, Alexandra (EdTech Hub, 2021)
This study explores the potential impact of interactive audio content for students and teachers delivered via Interactive Voice Response (IVR) in Ghana following the reopening of schools. The content for the lessons was drawn from the Rising On Air (ROA) audio library, a 20-week programme developed by Rising Academies to support student learning over the radio during Covid-19 pandemic-related school closures. Rising Academies’ 30 low-cost private primary schools, known as Omega schools, were included in a randomised controlled trial. Half of the schools were randomised to receive the student intervention and the other half to receive the teacher intervention. Of the total sample of 1,359 students, 719 students in Grades 4, 5 and 6 received daily audio lessons that focused on foundational numeracy skills. Of the total sample of 333 teachers, 160 teachers received weekly professional development sessions focused on the instruction of foundational reading. In the student intervention, no significant effect was found on students’ math skills and although the majority of students reported liking the intervention and wanting it to continue, engagement was a significant challenge. Results from the teacher intervention indicated an improvement in teachers’ understanding of phonemic awareness, phonics, and morphology. Teachers’ beliefs about their ability to improve student learning in the areas of reading and engagement also increased, but the potential impact on student outcomes was not measured. Differences between the student and teacher interventions suggest some important considerations for future interventions delivered via IVR and highlight some of the challenges as well as potential opportunities for more effective low-tech solutions. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

15 EdTech research papers that we share all the time - Moss, Caitlin (EdTech Hub, 2020)
We hope you saw our recent blog post responding to questions we often get about interesting large-scale EdTech initiatives. Another question we are often asked is: “What EdTech research should I know about?”  As Sara’s blog post explains, one of the Hub’s core spheres of work is research, so we ourselves are very interested in […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

Nepal “Ask me anything” Session: Responses to audience questions - Kaye, Tom; Groeneveld, Caspar; Moss, Caitlin; Haßler, Björn (EdTech Hub, 2020)
On Thursday, 30 April 2020, EdTech Hub participated in an 'Ask me anything' session for policymakers and funders in Nepal. The session focused on designing high-quality, effective, distance education programmes during the Covid-19 pandemic. Participants included high-level officials from the Nepalese government (e.g., the Ministry of Education, Science and Technology, the Curriculum Development Office, and the Education Review Office), representatives from development partners (e.g., the World Bank, UNICEF and USAID) and other education organisations (e.g., OLE Nepal). The session was convened for two purposes. First, to consider international good practice and current trends in distance education during the Covid-19 pandemic, presented by the World Bank EduTech team and EdTech Hub. Second, for the EdTech Hub team to gather questions from participants, to be able to target guidance specifically to the situation in Nepal. This document provides answers to a consolidated list of 10 questions received from stakeholders during the session. To consolidate any overlap, we have occasionally combined multiple questions into one. In other cases, where multiple important issues required a focused response, we split apart questions.
Keywords: C:Nepal; F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; docs.opendeved.net; dode_eth-src-dode; dode_eth-trf2-dode

Where do teachers go, and where do they stay? - Lurvink, Anne-Fleur; Espinoza-Revollo, Patricia; Ali, Yusuf; Garrod, Oliver; Atherton, Paul; Mackintosh, Alasdair; Ramirez, Ana; Beoku-Betts, Iman; Haßler, Björn; Godwin, Katie; Godwin, Anne-Fleur Lurvink, Patricia Espinoza-Revollo, Yusuf Ali, Oliver Garrod, Paul Atherton, Alasdair Mackintosh, Ana Ramirez, Iman Beoku-Betts, Björn Haßler and Katie (EdTech Hub, 2023)
In Sierra Leone, a government payroll position is tied to the teacher, not the school, meaning teachers can change schools once they go on the payroll. This leads to certain schools being chronically understaffed. It also suggests that deploying teachers to rural and understaffed schools (or putting teachers already there on payroll) might not tackle high pupil-to-qualified-teacher ratios in the longer term. Investigating the school-to-school movement of payroll teachers can help us understand where teachers go after they go on the payroll and how long they stay in a given school. We also looked at overall movement nationally to identify areas of the country that are outliers in terms of high and low retention of teachers.

Effectiveness of Multimodal Microlearning for In-Service Teacher Training - Allela, Melisa Achoko; Ogange, Betty Obura; Junaid, Muhammad Ibn; Charles, Prince Brainard (Journal of Learning for Development, 2020)
To meet the growing demand for continuing professional development of practising teachers, the integrated in-service teacher training (INSET) programme aims at making permanent improvements on the quality of teaching and learning for Junior Secondary School (JSS) Teachers in Sierra Leone. Within this context, a toolkit for School-Based Teacher Development was created and microlearning identified as an ideal mode to deliver the toolkit content. In this paper, we present the design considerations that informed this decision as well as challenges and lessons learned from the first implementation of the INSET project for junior secondary school teachers in Sierra Leone. A multimodal approach was considered and implemented to mitigate Internet access challenges and to expand learning opportunities. These include a mobile app version of the Toolkit, offline access to microlearning resources on the TeacherFutures platform via the Moodle mobile app, a mobile app version of one INSET module, an e-portfolio to be used by participants in sharing their learnings as demonstrated and practised during a face-to-face roll-out seminar, and finally, WhatsApp groups in which different schools engaged in discussions based on the questions on the Toolkit. Preliminary findings indicate a strong preference among participants for the use of WhatsApp as the main channel of communication within the communities of practice; and very limited use of the main e-learning Moodle platform and e-Portfolio. This necessitates a need to critically evaluate the effectiveness of the design of a multimodal approach for delivering microlearning content. From this, we seek to establish a set of design considerations, capacity building and technical support issues derived from analysis of data emerging from the ongoing project rollout. This will inform future integration of Microlearning resources in the teacher training project.
Keywords: Barriers; Communities of Practice; Electronic Learning; Foreign Countries; Inservice Teacher Education; Integrated Learning Systems; Internet; Multimedia Materials; Portfolios (Background Materials); Professional Continuing Education; Professional Development; Program Effectiveness; Secondary School Teachers; Social Media; Synchronous Communication; Teacher Collaboration; Teacher Competencies; Workshops

Data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia - Vijil, Alejandra; El-Serafy, Yomna; Adam, Taskeen; Haßler, Björn (EdTech Hub, 2024)
This report provides a landscape analysis of available data collection and visualisation tools in the education sector in sub-Saharan Africa and South Asia. Digital data collection has the potential to facilitate cost-effective, adaptable, timely and reliable data to inform decision-making. The value proposition of these tools, as opposed to paper-based data collection, is that they have the potential to save valuable time and resources, minimise errors, and facilitate the sharing of results. To develop this report, we reviewed 50 available tools, of which we reviewed four in depth, considering their uses, features, and challenges. This report offers key takeaways on the potential advantages and limitations of using digital data collection tools in the education sector in sub-Saharan Africa and South Asia. Key words: data collection, data visualisation, education, sub-saharan africa, south asia, landscape analysis An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Your Questions Answered: Using Technology to Support Gender Equity, Social Inclusion and Out-Of-School Learning - Allier-Gagneur, Zoé; Moss Coflan, Caitlin (EdTech Hub, 2020)
EdTech Hub participated in a Girls’ Education Challenge webinar in May 2020, which welcomed stakeholders from countries including the UK, Kenya, Zimbabwe, and Nepal. The session focused on issues regarding gender and social inclusion during the Covid-19 crisis. This document provides answers to a list of 10 questions received from stakeholders.
Keywords: F: Helpdesk response; L:Gender and education; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-dode

Cohort Learning Handbook - Nicholson, Bryony (EdTech Hub, 2024)
The Cohort Learning Handbook captures EdTech Hub’s approach to building cohorts on its Evidence-Led Entrepreneurship Course. The course aims to help entrepreneurs adopt and utilise evidence to learn and to scale their products and services. The Handbook is for individuals and organisations who support EdTech entrepreneurs (e.g., accelerators, entrepreneurship programmes, and funders). Building a cohort supports entrepreneurs to learn quickly and more confidently as a result of learning with, from, and alongside peers sharing the same experience. By ensuring that the learning journey is the most effective it can be, we ensure our work has the greatest impact. By facilitating a cohort journey for EdTech entrepreneurs, you can: - Leverage the unique power of a cohort to improve the learning experience and learning outcomes. - Diversify the support on offer. - Streamline and improve technical support that we often offer ventures. The handbook includes a list of resources and templates for you to use and covers a range of topics and practical suggestions from key principles and onboarding to graduation and supporting alumni. Keywords: cohort; community; learning; collective; incubators; accelerators An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

18 large-scale EdTech initiatives on our radar in 2020 - Moss, Caitlin (EdTech Hub, 2020)
During the EdTech Hub’s inception phase so far, one question we hear a lot is: “What interesting or notable EdTech initiatives are you seeing?” Another question usually follows: “Which ones are reaching scale?” This week we have joined the global education community in London for the Education World Forum and BETT meetings. This is a […]
Keywords: F:Blog post; LP: English; _DOILIVE; _EdTechHub_Output; _zenodoETH

EdTech and Covid-19: 10 Things to Know - Nicolai, Susan; Wilson, Samuel; Jefferies, Kate (EdTech Hub, 2021)
EDTECH AND COVID-19 10 THINGS TO KNOW Covid-19 has reshaped our world. In education, mass school closures have accelerated the global use of education technologies. Yet the benefits do not reach everyone. Since the start of the pandemic, EdTech Hub and its partners have been researching and applying evidence on what works in technology for education in different contexts. Here…
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Session 4: How can I rapidly upskill my large teacher workforce? - Koomar, Saalim; Proctor, Jamie (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Data Access and Protection Laws in Pakistan: A technical review - Halim, Waqas; Upadhyay, Arjun; Coflan, Caitlin (EdTech Hub, 2022)
The advancement of technologies has supported an exponential rise in the collection and use of data. Data, when used appropriately, can support better decision-making and inform innovation. Data has value to entrepreneurs and innovators who seek to design products that respond to user needs. However, the widespread collection and use of data have also spawned concerns about individual rights and data privacy. Issues related to collection, usage, dissemination, and access to data have also come to the forefront. To address these concerns, many countries across the globe have introduced data protection laws. This policy brief identifies and analyses global best practices in data protection and data access. It is developed in response to an inquiry related to data and research in the education sector, specifically in Pakistan. The brief explores the potential practical challenges in the enforcement and implementation of global good practices in the context of the data protection environment in Pakistan; it proposes a set of key recommendations for the Government of Pakistan, provincial governments, development partners, and other education-related ministries and public departments. Keywords: Data protection (laws), good practices, data access, privacy rights, children's data, sensitive data, data-driven policy, data integration, third-party data sharing, open data, data security, data governance, encryption An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Annual School Census Report - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)
Keywords: auto_merged

2022 Annual School Census Report - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2023)

The Sandbox Handbook v1.0: A guide to growing and testing EdTech ideas - Rahman, Asad; Carter, Alice; Plaut, Daniel; Dixon, Dixon; Salami, Taiye; Schmitt, Laurel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _r:AddedByZotZen; _zenodo:submitted

Using EdTech in Settings of Fragility, Conflict and Violence: A Curated Resource List - Koomar, Saalim; Moss Coflan, Caitlin; Kaye, Tom (EdTech Hub, 2020)
This curated list of resources collates interventions that effectively deploy education technology in settings of fragility, conflict and violence (FCV). This list explores effective uses of EdTech in FCV settings, emphasising interventions and evidence relevant to the Yemeni context and distance learning during the Covid-19 crisis.
Keywords: C:Yemen; F: Helpdesk response; LP: English; W:Fragile and conflict affected contexts; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Les Technologies De L’enseignement Et Le Covid-19 - 10 Choses À Savoir - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Using Interactive Radio Instruction to Mitigate the Educational Impact of Covid-19: A curated resource list - McBurnie, Chris (EdTech Hub, 2020)
Interactive Radio Instruction (IRI) is a distance education tool that enables educators to use radio broadcasts to direct active learning in the home. This curated list of resources aims to inform and support the use of IRI to mitigate the educational impact of Covid-19.
Keywords: COV:COVID and reopening of schools; F: Helpdesk response; H:Radio; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of emerging country-level response to providing educational continuity under COVID-19: What are the lessons learned from supporting education for marginalised girls that could be relevant for EdTech responses to COVID-19 in lower- and middle-income countries? - Naylor, Ruth; Gorgen, Kristine (EdTech Hub, 2020)
Keywords: COV:COVID and reopening of schools; L:Gender and education; LP: English; _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; ___working_potential_duplicate; _cover:other:ok; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; ⛔ No DOI found

Open Educational Resources in Africa: A Curated Resource List - Koomar, Saalim; Jull, Stephen (EdTech Hub, 2020)
This curated list defines Open Rducational Resources (OER), offers background on open-source licensing, and provides a review of OER that can be used in the sub-Saharan African context.
Keywords: C: Ghana; F: Helpdesk response; H: Open resources; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH

Guidance on Pre-Assessment for Establishing E-Learning Centres - AlSheikh Theeb, Thaer; McGinty, Sara; Obaid, Rasha (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Session 3: How can I develop an aligned and actionable EdTech strategy - Wyss, Natalie; Mbugua, Wanjiku; Kaye, Tom (2022)
The Strategic Choices for Education Reform workshop held in Zimbabwe in November 2022 aimed to provide a forum for senior government officials to reflect and consider the strategic reform options for their countries. The objective was to convene officials in key positions in the ministries of education, higher education, finance, and planning to learn about important issues and approaches in education; exchange experiences and lessons; develop an understanding of what is necessary to reconstruct better and more resilient education systems; and to transform the large potential of young people, through human capital investments, into development and prosperity. EdTech Hub was invited to facilitate the day of the workshop focused on harnessing ICT for better teaching and learning. This presentation is one of several used in the workshop to promote learning, discussion, and problem solving among the participants. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Education during the COVID-19: crisis Opportunities and constraints of using EdTech in low-income countries - Jordan, Katy; David, Raluca; Phillips, Toby; Pellini, Arnaldo (Revista de Educación a Distancia (RED), 2021)
The Covid-19 pandemic has ushered in a period of educational disruption on an unprecedented scale. During this time of crisis, education will not be business as usual, and EdTech alone cannot close the learning gap. It will be dedicated teachers and resilient educators who will ensure learning doesn’t st op — but they could be helped by the right EdTech tools. However, the digital divide means that internet and mobile network access varies greatly in middle and low - income countries. In this discussion paper, we explore some of the key constraints of using EdTech at scale to support education in low - income countries at a time of crisis, and highlight the opportunities that have so far emerged, in a rapidly - changing context. We draw upon evidence and examples to inform policy and programming decisions, moving from the initial emergency response to building resilience in the longer term, and planning to diagnose and treat the learning gaps that have emerged during the crisis.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; países de bajos ingresos

The Economic Lives of Young Women in the Time of Ebola: Lessons from an Empowerment Program - Bandiera, Oriana; Buehren, Niklas; Goldstein, Markus; Rasul, Imran; Smurra, Andrea (World Bank, 2018)
We evaluate an intervention to raise young women’s economic empowerment in Sierra Leone, where women frequently experience sexual violence and face multiple economic disadvantages. The intervention provides them with a protective space (a club) where they can …nd support, receive information on health/reproductive issues and vocational training. Unexpectedly, the post-baseline period coincided with the 2014 Ebola outbreak. Our analysis leverages quasi-random across-village variation in the severity of Ebola-related disruption, and random assignment of villages to the intervention to document the impact of the Ebola outbreak on the economic lives of 4 700 women tracked over the crisis, and any ameliorating role played by the intervention. In highly disrupted control villages, the crisis leads younger girls to spend signi…cantly more time with men, out-of-wedlock pregnancies rise, and as a result, they experience a persistent 16pp drop in school enrolment post-crisis. These adverse e¤ects are almost entirely reversed in treated villages because the intervention enables young girls to allocate time away from men, preventing out-of-wedlock pregnancies and enabling them to re-enrol in school post-crisis. In treated villages, the unavailability of young women leads some older girls to use transactional sex as a coping strategy. The intervention causes them to increase contraceptive use so this does not translate into higher fertility. Our analysis pinpoints the mechanisms through which the severity of the aggregate shock impacts the economic lives of young women, and shows how interventions in times of crisis can interlink outcomes across younger and older cohorts. JEL Classi…cation: I25, J13, J24.
Keywords: ___working_potential_duplicate

Proposal to the Global Partnership for Education for a contribution towards the implementation of the 2018-2020 Education Sector Plan - Ministry of Education, Science and Technology (Government of Sierra Leone; UNICEF, 2018)

Consequences of school closure on access to education: lessons from the 2013–2016 Ebola pandemic - Smith, William C. (International Review of Education, 2021)
The COVID-19 pandemic has seen an unprecedented shutdown of society. Among the various safety measures taken, much attention has been given to school closure as a non-pharmaceutical mitigation tool to curb the spread of the disease through ensuring “social” (physical) distancing. Nearly 1.725 billion children in over 95% of countries worldwide have been affected by school closures implemented in April 2020 as the virus continued to spread. In the field of education, policymakers’ attention has been directed at keeping students on board through remote learning and addressing the immediate needs of schools upon reopening. The study presented in this article focuses on who remains absent after schools resume. Using publicly available survey data from the USAID Demographic Health Surveys Program and the UNICEF Multiple Indicator Cluster Survey from before and after the 2013–2016 Ebola pandemic in Guinea and Sierra Leone in West Africa, the author examined changes in school enrolment and dropout patterns, with targeted consideration given to traditionally marginalised groups. At the time, schools closed for between seven to nine months in the two countries; this length and intensity makes this Ebola pandemic the only health crisis in the recent past to come close to the pandemic-related school closures experienced in 2020. The author’s findings suggest that post-Ebola, youth in the poorest households saw the largest increase in school dropout. Exceeding expected pre-Ebola dropout rates, an additional 17,400 of the poorest secondary-age youth were out of school. This evidence is important for minimising the likely post-COVID-19 expansion in inequality. The author’s findings point to the need for sustainable planning that looks beyond the reopening of educational institutions to include comprehensive financial support packages for groups most likely to be affected.

EdTech Policy Rapid Scan for Sub-Saharan Africa - Flam, Rebekka; Oyedele, Oluwatomisin (EdTech Hub, 2025)
This rapid scan presents a curated list of EdTech policies in sub-Saharan Africa, compiled in response to a request from the World Bank. Based on desk research from mid-2024, it highlights that most policies predate COVID-19, with few new ones emerging post-2020. Many countries lack dedicated EdTech policies, instead relying on broader ICT or education strategies. Common themes include digital infrastructure, distance learning, and teacher training, while gaps remain in support for marginalised learners. The report provides an overview of existing policies, while the highlighted trends offer insights for future policy development. Keywords: EdTech policy; education policy; sub-Saharan Africa; EdTech governance; digital learning; digital infrastructure An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Pakistan Topic Brief: Providing Distance Learning to Hard-to-reach Children - Baloch, Imdad; Kaye, Tom; Koomar, Saalim; McBurnie, Chris (EdTech Hub, 2020)
This brief explores the use of EdTech to support distance learning in Pakistan. Specifically, it explores ways to provide distance education to children in remote rural areas and urban slums.
Keywords: F: Helpdesk response; L:Out-of-school populations; LP: English; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; _cover:v1; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech evidence for Covid-19 response: Rapid evidence reviews of EdTech use in low-income and crisis contexts - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _r:AddedByZotZen; _zenodo:submitted

Engaging Girls with E-Learning: A curated list of good practices - AlSheikh Theeb, Thaer (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: Helpdesk Response; _r:AddedByZotZen

EdTech to Reach the Most Marginalised: A Call to Action - Zubairi, Asma; Kreimeia, Adam; Jefferies, Kate; Nicolai, Susan (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; ___working_potential_duplicate; _r:AddedByZotZen; _zenodo:submitted

2019 Annual School Census Report - Ministry of Basic and Senior Secondary Education (Ministry of Basic and Senior Secondary Education, 2019)

تكنولوجيا التعليم وجائحة كوفيد 19 - .10 أشياء يجب معرفتها - EdTech Hub Team (2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

EdTech That Reaches Marginalised Learners: Relevant Examples for the Indonesian Context - Rui, Yang (Tingting); Upadhyay, Arjun (EdTech Hub, 2022)
This curated list of resources presents a sample of education technology programmes that effectively reach marginalised learners, including children with SEND, girls, and children in frontier, outermost, and disadvantaged regions. This list provides short summaries of lessons in using EdTech such as radio, television, and mobile phones to reach marginalised learners, emphasising interventions and evidence relevant to the Indonesian context. Keywords: marginalised learners, Indonesia, radio, television, mobile phones, girls, no-tech options An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Mapping National Digital Learning Platforms - Rui, Tingting; Chuang, Rachel; Thinley, Sangay; AlSheikh Theeb, Thaer; Villavicencio, Xuzel; Rasolohery, Hasiniavo (EdTech Hub, 2023)
This report presents findings from a global mapping exercise of 471 national digital platforms across 184 countries that was conducted by EdTech Hub following a Helpdesk request from UNICEF. The mapping exercise focused on examining three key areas of availability, usability, and inclusivity of national digital learning platforms. The study found that 32% of identified national digital learning platforms no longer exist, have not been updated since 2020, or have links that do not work. Only 30% of platforms offer offline functionality. Eighty-five per cent of platforms were accessible on a basic smartphone. This report serves as a snapshot in time of national digital learning platforms around the world. Future mapping exercises and reports may be carried out to expand on this work. Keywords: platforms, digital, learning, mobile, mapping, offline An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Inequalities in Girls’ Learning Opportunities via EdTech: Addressing the Challenge of Covid-19 - Crompton, Helen; Chigona, Agnes; Jordan, Katy, Jordan; Myers, Christina (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _r:AddedByZotZen

10 principles to consider when introducing ICTs into remote, low-income educational environments - Trucano, Michael (World Bank Blogs, 2013)
there must be an I, a C, and a T here somewhere ... There are, broadly speaking, two strands of concurrent thinking that dominate discussions around the use of new technologies in education around the world. At one end of the continuum, talk is dominated by words like 'transformation'. The ...

Policy Guidelines on School Approvals - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)

National Policy on Radical Inclusion in Schools - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2021)

National Policy on Radical Inclusion in Schools Implementation Plan 2021-2026 - Ministry of Basic and Senior Secondary Education (Government of Sierra Leone, 2022)

Artificial Intelligence and Education Systems in 2035: Fourteen trends and five scenarios for how the future might unfold - Rahman, Asad; Freeman, Abigail (EdTech Hub, 2025)
This strategic foresight study aims to understand the shifts that might take place in education systems in low- and middle-income country (LMIC) contexts, given developments in artificial intelligence (AI) that might occur over the next 10 years. It begins by capturing fourteen trends, relating to AI that might affect the development of education systems in LMICs. After identifying trends, we combined them to sketch five concrete, tangible scenarios. This understanding will inform a multi-year programme of work, addressing how LMICs can strengthen their capacity, in light of such future possibilities. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

The effect of Covid-19 on education in Africa and its implications for the use of technology - eLearning Africa; EdTech Hub (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH

Transforming Education Service Delivery Through Evidence-Informed Policy and Practice - The Ministry of Basic and Senior Secondary Education (MBSSE) (The Ministry of Basic and Senior Secondary Education (MBSSE), 2021)

EdTech and Covid-19: Insights from our Sandbox Portfolio. In Collaboration with Sandbox Partner Organisations - Rahman, Asad; Plaut, Daniel; Salami, Taiye; Carter, Alice (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

EdTech for Climate Resilience: A Rapid Evidence Review - Brugha, Meaghan; Afzal, Nimra; Emerusenge, Aime Parfait; Zazai, Rozina; Nagol, Elias (EdTech Hub, 2025)
This Rapid Evidence Review provides a synthesis of evidence related to the use of educational technology for building climate resilience within education systems in low- and middle-income countries. The primary objective of the review is to provide educational stakeholders with an overview of how technology could be effectively leveraged in these contexts, highlighting key design considerations for and potential barriers to effective implementation. The review looked at evidence generated between 2014 and 2025 on how EdTech has or could be used to build climate resilient education systems. An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

How EdTech Can Be Used to Help Address the Global Learning Crisis: A Challenge to the Sector for an Evidence-Driven Future - Hollow, David; Jefferies, Kate (EdTech Hub, 2022)
Keywords: ⛔ No INSPIRE recid found

Developing a national EdTech strategy - Coflan, Caitlin; Wyss, Natalie; Thinley, Sangay; Roland, Mark (EdTech Hub, 2022)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

Building an Acceptable Use Policy - Tanweer, Rabia; Wyss, Natalie (EdTech Hub, 2023)
Acceptable use policies (AUPs) aim to define how digital and technological tools and services (both devices and ICT services) should be used in or by education systems and actors. These policies address the rights, privileges, responsibilities, and ramifications associated with the use of technology in education spaces and for educational purposes. In doing so, AUPs attempt to promote good practice and responsible, safe use of the internet and digital technologies. This brief uses global examples of AUP policies and guidance on the development of AUPs to outline best practices and key considerations for the development of AUPs. Keywords: EdTech usage; acceptable use policy; tablets; laptops; desktop computers; EdTech hardware; EdTech software. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Methodology for literature reviews - Haßler, Björn; Adam, Taskeen; Allier-Gagneur, Zoe; Blower, Thomas; Brugha, Meaghan; Damani, Kalifa; Hennessy, Sara; Martin, Kevin; Megha-Bongnkar, Ghislaine; Murphy, Mary; Walker, Hannah; Walker, Hannah (EdTech Hub, 2021)
An output of the EdTEch Hub
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)

An international review of plans for school reopening - Gorgen, Kristine; McAleavy, Tony (Education Development Trust, 2020)
Keywords: auto_merged

Lessons learnt from education data mapping in Africa: Workshop summary and synthesis - Pambe, Rigobert; Kadzamira, Esme; Mjomba, Renaldah; Lawson, Laté; Onsomu, Eldah; Adam, Taskeen; Heady, Lucy; Mugo, John; Tinto, Teg-WendeIdriss (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Community Help for Inclusive Learning and Development (CHILD): A Study of How Mobile Phones Were Used to Recruit and Equip Community Volunteers to Support Children’s Learning During Covid-19 School Closures in Zimbabwe - Power, Tom; Buckler, Alison; Ebubedike, Margaret; Tengenesha, Martha; Jama, Mbuso; Ndlovu, America; Mukoyi, Jane; Ndou, Mashudu; Mubaira, Simbarashe (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH

Country list with HDI, iHDI, MPI and Gini (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
This is pdf of a country list with HDI, iHDI, MPI and Gini. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB (which will also be available as a data file).
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:q; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Using Technology to Improve Education for Marginalised Girls: Lessons in implementation from the Girls’ Education Challenge - Anonymised for Peer Review Purposes (EdTech Hub, 2023)
This article presents the findings of an in-depth study on the implementation of six EdTech-supported projects within the UK Government Foreign, Commonwealth and Development Office (FCDO)’s Girls’ Education Challenge portfolio, which aims to improve education for the world’s most marginalised girls. Using primary key informant interviews and secondary data from sampled projects, the study identifies the core components related to the implementation of EdTech within the sampled projects: evidence-informed design and delivery; building and maintaining relationships across and between stakeholders; comprehensive and continuous training and capacity development; and situating EdTech within a broader holistic model that prioritises gender inclusion to optimise implementation for marginalised girls. In doing so, the study provides key lessons for optimising the future implementation of EdTech for marginalised girls. Keywords: educational technology; girls’ education; programme implementation; Covid-19 An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Mission and Vision - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education Republic of Sierra Leone, Government of Sierra Leone, 2018)

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Eight Reasons Why EdTech Doesn’t Scale: How sandboxes are designed to counter the issue - Simpson, Lea; Carter, Alice; Rahman, Asad; Plaut, Daniel (EdTech Hub, 2021)
The EdTech Hub’s sandbox approach offers implementers and decision makers a clear way to implement and scale only the most effective EdTech interventions. In this position paper we share our view on why EdTech isn’t scaling and how we see the sandboxes approach addressing them. Keywords: innovation; implementation; sandboxes; EdTech; scale; experimentation An output of the EdTech Hub, https://edtechhub.org
Keywords: _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen

Problem Analysis and Focus of EdTech Hub’s Work: Technology in education in low- and middle-income countries - Hennessy, Sara; Jordan, Katy; Wagner, Daniel A.; EdTech Hub Team (EdTech Hub, 2021)
Keywords: _C:Afghanistan AFG; _C:Bangladesh BGD; _C:Botswana BWA; _C:Congo, Democratic Republic COD; _C:El Salvador SLV; _C:Gambia GMB; _C:Germany DEU; _C:Ghana GHA; _C:India IND; _C:Indonesia IDN; _C:Ireland IRL; _C:Jordan JOR; _C:Kenya KEN; _C:Lebanon LBN; _C:Liberia LBR; _C:Malawi MWI; _C:Pakistan PAK; _C:Peru PER; _C:Philippines PHL; _C:Rwanda RWA; _C:Senegal SEN; _C:Sierra Leone SLE; _C:South Africa ZAF; _C:Tanzania TZA; _C:Uganda UGA; _C:United Kingdom GBR; _C:United States USA; _C:Uruguay URY; _C:Zambia ZMB; _C:eSwatini SWZ; _DOILIVE; _EdTechHub_Output; _MELA_seen; __C:scheme:1; ___working_potential_duplicate; _cover:v3; _zenodo:submitted; _zenodoETH; ⛔ No INSPIRE recid found

Impact de la pandémie de COVID-19 sur l’éducation en Afrique et incidence sur le recours aux technologies: Sondage sur l’expérience et les opinions des éducateurs et spécialistes de technologies - eLearning Africa; EdTech Hub (2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _zenodo:submitted; _zenodoETH; ⚠️ Invalid DOI

EdTech Innovation for COVID-19: Insights from our global call for ideas - Plaut, Daniel; Carter, Alice; Dixon, Miranda; Salami, Taiye (EdTech Hub, 2020)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _zenodo:submitted; _zenodoETH

Messaging Apps, SMS, and Social Media: A Rapid Evidence Review - Jordan, Katy; Mitchell, Joel (EdTech Hub, 2020)
This Rapid Evidence Review (RER) provides an overview of existing research on the use of mobile phone-based messaging (including SMS, and messaging through apps such as WhatsApp) to support education in low- and middle-income countries (LMICs). This topic was chosen as the focus for a RER in response to the Covid-19 pandemic and school closures, as this form of technology has been adopted as part of some countries’ methods of providing continuing education during closures and disruption. As such, the overall purpose of this document is to summarise the existing research literature around messaging, so that the existing evidence can be used to inform ongoing responses to the pandemic. The findings are intended to be of use to educational decision makers, including donors and those in government and NGOs, to inform responses to the current pandemic.
Keywords: Covid-19; LMICs; SMS; Social media; TPD; WhatsApp; _DOILIVE; _EdTechHub_Output; _GS:indexed; _MELA_seen; ___working_potential_duplicate; _cover:v3; _r:CopiedFromEvLib; _zenodo:submitted; _zenodoETH; educational technology; mobile learning; refugee education; teacher professional development; text message; ⛔ No DOI found

Delivering Remote Learning Using a Low-Tech Solution: Evidence from an RCT during the Covid-19 Pandemic - Islam, Asad; Wang, Liang Choon; Hassan, Hashibul (EdTech Hub, 2022)
During the prolonged school closure due to the Covid-19 pandemic, many children in rural Bangladesh were missing out on formal education. What is more these children had limited access to distance learning modalities such as the internet, television, and radio. To counteract this poor access, this study used the widely accessible modality of mobile phones to deliver a set of audio lessons to primary school students using Interactive Voice Response (IVR). These lessons were developed using the Interactive Radio Instruction (IRI) method. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

EdTech to Support Out-of-School Children and Adolescents - Thinley, Sangay; Rui, Yang (EdTech Hub, 2023)
This Helpdesk report was created in response to a request from the World Bank Malawi Education Team for a curated list of resources on examples of EdTech interventions targeting out-of-school children and adolescents to inform an ASA (Advisory Services and Analytics) output. The ASA output will provide policy options to improve second-chance learning and foundational skills for out-of-school children (OOSC). To provide the World Bank Malawi team with adequate information on the above. This curated list begins with an introduction to the use of EdTech to support out-of-school children and youth, and then moves on to present examples of such interventions and programmes within Malawi, as well the wider African region and the rest of the world. This list is designed to serve as a resource for the team and does not make any direct recommendations on actions to be taken. An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen; ⛔ No INSPIRE recid found

About the Ministry – Ministry of Communication, Technology & Innovation - Ministry of Communication, Technology & Innovation (Ministry of Communication, Technology & Innovation, Government of Sierra Leone, 2024)

Statement from the Minister - Ministry of Technical & Higher Education (Ministry of Technical & Higher Education, Government of Sierra Leone, 2018)

Flagship Projects - Directorate of Science, Technology & Innovation (Directorate of Science, Technology & Innovation, Government of Sierra Leone, 2023)

Low-Tech Devices and Connectivity for Learning in Lebanon - Chuang, Rachel; Khalayleh, Abdullah (EdTech Hub, 2021)
This document was produced in response to a request from the FCDO Lebanon team for guidance on leveraging low-tech devices and enabling connectivity to support learners in Lebanon, aligning with school reopenings. The document compiles effective initiatives across Lebanon and other countries.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

EdTech to Support Blended Learning in Mozambique: A curated list of EdTech interventions - Flam, Rebekka; Ramesh Vasudevan, Sharanya; Coutrim, Erica (EdTech Hub, 2024)
This document was produced in response to a request from the UNICEF Mozambique country office submitted to the EdTech Hub Helpdesk in November 2023. The UNICEF team requested a curated list of blended learning approaches and resources that are relevant to the Mozambique context, with a special focus on resources that are implemented or sourced from the Eastern and Southern Africa region. In response, the EdTech Hub Helpdesk has created this report to provide contextual and background information on the blended learning landscape in Eastern and Southern Africa, with a specific focus on Mozambique, along with a list of resources on blended learning. Keywords: blended learning; hybrid learning; Africa; Mozambique An output of the EdTech Hub, https://edtechhub.org/
Keywords: _r:AddedByMyEducationEvidence

Voices and Evidence from End-Users of the GLTV and GLRRP Remote Learning Programme in Ghana: Insights for inclusive policy and programming - Hodor, Raymond; Owusu, Ernest Adu; Ofori-Davis, Lucy; Afram, Alexander; Sefa-Nyarko, Clement (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Monitoring Distance Education: A Brief to Support Decision-Making in Bangladesh and Other Low- and Lower-Middle-Income Countries - Kaye, Tom; Groeneveld, Caspar; Bashir, Amreen (EdTech Hub, 2020)
This brief outlines a model for monitoring and evaluating distance learning based on a desktop review of interventions during the Covid-19 school closures and other previous school shutdowns. It then examines how this might be applied in the Bangladeshi context.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; ___working_potential_duplicate; _zenodo:submitted; _zenodoETH; dode_eth-src-dode; dode_eth-trf2-dode; ⛔ No INSPIRE recid found

EdTech and COVID-19 response [Save Our Future] - Haßler, Björn; Nicolai, Susan; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (#SaveOurFuture, 2020)
This document is background paper 3 for the #SaveOurFuture campaign. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. This document is also available as an EdTech Hub report, see https://docs.edtechhub.org/lib/IA9PL99D
Keywords: _DOILIVE; _EdTechHub_Output; _GS:not_indexed; _MELA_seen; _cover:other:ok; _cover:v2; _r:CopiedFromEvLib; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

EdTech and COVID-19 response [EdTech Hub Report] - Haßler, Björn; Nicolai; McBurnie, Chris; Jordan, Katy; Wilson, Sam; Kreimeia, Adam (EdTech Hub, 2020)
This document is background paper 3 for the #SaveOurFuture campaign as an EdTech Hub report. The full paper and other working group papers are available here: https://saveourfuture.world/white-paper/. The evidence library entry for the background paper in original format is https://docs.edtechhub.org/lib/SXDQAPB6.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:other:ok; _cover:v2; _yl:j; _yl:k; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

The Maldives and Sri Lanka: Question & Answer Session - Adam, Taskeen; Kaye, Tom; Haßler, Björn (EdTech Hub, 2020)
EdTech Hub participated in a question and answer session in May 2020 for policymakers in The Maldives and Sri Lanka. The session focused on the challenges and issues in designing effective distance education programmes during the Covid-19 pandemic. This document provides answers to a list of 13 questions received from stakeholders.
Keywords: F: Helpdesk response; LP: English; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v1; _zenodo:submitted; _zenodoETH; dode_eth-src-eth; dode_eth-trf2-dode

Overview of Emerging Country-Level Response to Providing Educational Continuity Under COVID-19 - Hallgarten, Joe; Gorgen, Kristine; Sims, Kate (Education Development Trust, 2020)
Keywords: ⛔ No DOI found

About the MBSSE - Ministry of Basic and Senior Secondary Education (Ministry of Basic and Senior Secondary Education, Government of Sierra Leone, 2024)

Developing a Proof of Concept for a Regional Learning Hub for Eastern and Southern Africa Part 4: Content curation - Groeneveld, Caspar (EdTech Hub, 2022)
In 2021 the UNICEF Eastern and Southern Africa Regional Office (ESARO), UNESCO, UNHCR, the Inter-agency Network for Education in Emergencies (INEE) and EdTech Hub began collaborating to develop a Regional Learning Hub (RLH). The aim of the RLH is to create a platform to provide teaching and learning content aligned to the curricula of different countries in the region that is appropriate to local contexts. The RLH is envisaged as a platform where digital learning content has been pre-aligned with national curricula to enable use by governments and education stakeholders to facilitate quick selection of content for educational use in their regions. This document is the fourth of five reports on the development of a proof of concept for the Hub and describes our observations during content curation. We recommend beginning with the Final report and then moving to any of the remaining four reports, depending on your interest: Inception report User research Skills taxonomy Content curation An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Technology, Teacher Professional Development and Low- and Middle-Income Countries: Technical report on systematic mapping review - Hennessy, Sara; D'Angelo, Sophia; McIntyre, Nora; Koomar, Saalim; Kreimeia, Adam; Cao, Lydia; Brugha, Meaghan; Zubairi, Asma (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: ___working_potential_duplicate; _r:AddedByZotZen

Syṡtemic Mixed-Methods Research — a conceptual framework for scalable EdTech research - Haßler, Björn; El-Serafy, Yomna; Khalayleh, Abdullah; McBurnie, Chris (EdTech Hub, 2021)
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:v3; _yl:n; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Desk Review of Technology-Facilitated Learning in Pakistan: A review to guide future development of the technology-facilitated learning space in Pakistan - Wilson, Sam; Khalayleh, Abdullah; Baloch, Imdad; Kaye, Tom (EdTech Hub, 2022)
During the Covid-19 pandemic, EdTech has been used in many different ways to keep children learning in Pakistan. This has ranged from educational radio broadcasting to children in remote mountains, to TV channels being used to deliver classes nationwide. Yet, as the pandemic has developed, this picture has become more complex. Optimism in EdTech’s promise has given way to fears that the most marginalised children — particularly those who cannot access technological solutions — are falling further behind. Even those children who are able to use EdTech may not be learning. In short, a pre-existing digital divide has become more pronounced now that education delivery has had to increasingly rely on technology. This divide must be addressed if EdTech is to support effective learning for all children in all contexts in Pakistan. This desk review argues that the only way to realise EdTech’s potential is to recognise its shortcomings. Technology alone will not help children learn. EdTech’s role is as one part of a wider education system. Technology facilitates learning with support from key actors such as parents, teachers, and school leaders and with sustained political support and supporting infrastructure. This review provides an overview of Pakistan’s technology-facilitated learning landscape that caters to the learning needs of children aged 6–16. It sets out key EdTech-related features, challenges and trends, in addition to highlighting prominent EdTech organisations and tools in Pakistan. Keywords: infrastructure; low tech; policy; out-of-school children; marginalised learners; Pakistan; MoFEPT; UNICEF An output of the EdTech Hub, https://edtechhub.org
Keywords: _r:AddedByZotZen

Effective Use of EdTech for Remedial Learning Programmes: Considerations for Mongolia - Upadhyay, Arjun; Shoobridge, James; Moss Coflan, Caitlin (EdTech Hub, 2020)
This document was produced in response to a request from the World Bank Mongolia team to: 1. Outline the evidence of effective practices on remedial education generally. 2. Explore appropriate uses of EdTech to support remedial education. 3. Summarise the implications of these findings for Mongolia.
Keywords: F: Helpdesk response; _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _zenodo:submitted

Teacher professional development in sub-Saharan Africa: Equity and scale [preprint] - Haßler, Björn; Bennett, Gemma; Damani, Kalifa (2020)
This chapter synthesises approaches to teacher professional development based on the evidence provided by three key reviews. A comprehensive and pragmatic set of eight principles for teacher professional development in sub-Saharan Africa is presented, including recommendations for: effective teaching and learning practices that facilitate a focus on student learning; professional status and motivation of teachers; design and conduct of professional development programmes; and the value of appropriate Open Educational Resources / Practices and the wise use of educational technology, as well as considerations for policy formulation. We argue that these features can be realised through holistic school-based peer-facilitated TPD models which is not only not only educationally effective, but also cost-effective and scalable. Such models have the potential to radically increase equitable participation in education.
Keywords: C:sub-Saharan Africa; _yl:t; dode_eth-src-dode; dode_eth-trf2-dode

The Power of Girls' Reading Camps: Exploring the impact of radio lessons, peer learning and targeted paper-based resources on girls’ remote learning in Kenya - Amenya, Donvan; Fitzpatrick, Rachael; Njeri, M.E.; Naylor, Ruth; Page, Ella; Riggall, Anna (EdTech Hub, 2021)
An output of the EdTech Hub, https://edtechhub.org
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _r:AddedByZotZen; _zenodo:submitted

Sustaining and scaling pedagogic innovation in sub-Saharan Africa: Grounded insights for teacher professional development - Haßler, Björn; Hennessy, Sara; Hofmann, Riikka (Journal of Learning for Development, 2018)
Developing sustainable and scalable educational initiatives is a key challenge in low-income countries where donor-funded short-term projects are limited by both contextual factors and programme design. In this concept paper we examine some of the issues related to in-service teacher development in the context of sub-Saharan Africa, grounded predominantly in our experiences of over 5 years of iteratively developing, refining and evaluating an intensive school-based professional learning programme for primary school teachers. “OER4Schools” integrates interactive pedagogy, Open Educational Resources (OER) and use of mobile devices (where available). The focus of this paper is on identifying what the main factors are perceived to be in sustaining and scaling up such a programme, from the perspectives of participating teachers, workshop facilitators and the research team. Synthesising our previous research and drawing on recent work in the field, we identify the key characteristics of effective and sustainable professional learning in low-resourced contexts. Such characteristics include effective peer facilitation, school-based active learning, explicit programme structure, appropriate scheduling and resourcing, and mitigating resource constraints through use of OER. Our conclusions thereby offer insights concerning the importance and impact of wider influences on participation and engagement of stakeholders and lead to recommendations for programme design and implementation, that should be taken on board by future initiatives.
Keywords: AWP2; Active Learning; Africa; Author:Haßler; C:sub-Saharan Africa; CitedIn:DFID_SRF; CitedIn:OER4S-TPE-Anon; CitedIn:OER4Schools-2012-HHH1-anon; CitedIn:PhD_Thesis; DIAL-RDO; Developing Nations; Educational Technology; Elementary Secondary Education; Faculty Development; Foreign Countries; Handheld Devices; IMPORT_FROM_DFID_RITE; InPrep; Inservice Teacher Education; Low Income Groups; Motivation; OER4Schools; Open Educational Resources; Peer Teaching; RPF-May-2016; Resource Allocation; Rural Schools; Scaffolding (Teaching Technique); Scheduling; Shared Resources and Services; Sustainable Development; Sustainable Development Goal 4; Teacher Professional Development; Technology Uses in Education; Telecommunications; ___working_potential_duplicate; dode_eth-src-dode; dode_eth-trf2-dode; missingHU; peer-facilitation; school-based active learning; sub-Saharan Africa; ⛔ No DOI found

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets